Resin composition, resin sheet, prepreg and printed wiring board

By using a combination of materials such as maleimide and polyphenylene eter in the insulating layer of the printed circuit board, the shortcomings of the printed circuit board in the prior art in terms of high-frequency signal processing and thinning are solved, and the effects of low dielectric constant, low dielectric loss and high-frequency signal transmission are achieved.

JP7660078B2Active Publication Date: 2025-04-10MITSUBISHI GAS CHEM CO INC +1

Patent Information

Application Number
JP2021572773
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-25
Filing Date
2021-01-20
Publication Date
2025-04-10
Estimated Expiration
2041-01-20

AI Technical Summary

Technical Problem

The insulation layer of existing printed circuit boards has shortcomings in thinning and high-frequency signal processing, and it is difficult to achieve the requirements of low dielectric constant, low dielectric loss and high-frequency signal transmission simultaneously.

Method used

The dielectric and mechanical properties are optimized by combining a resin combination containing a maleimide compound, a specific polyphenylene eter compound and a styrene backbone.

Benefits of technology

It realizes the effects of low dielectric constant, low dielectric loss and high frequency signal transmission, while improving the flexibility and peel strength of the material, and is suitable for high-density and high-integration electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660078000001
    Figure 0007660078000001
  • Figure 0007660078000002
    Figure 0007660078000002
  • Figure 0007660078000003
    Figure 0007660078000003
Patent Text Reader

Abstract

[Problem] To provide: a resin composition with which excellent low permittivity properties, low dielectric dissipation properties, flexibility, and peel strength can be obtained; a resin sheet; a prepreg; and a printed wiring board. [Solution] A resin composition containing: a maleimide compound (A) that exhibits a relative permittivity of less than 2.7; a polyphenylene ether compound (B) that is represented by general formula (1) and has a number-average molecular weight of 1,000 to 7,000; and a block copolymer (C) that has a styrene skeleton. In general formula (1), X represents an aryl group, -(Y-O)n2- represents a polyphenylene ether moiety, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer of 1-100, n1 represents an integer from 1 to 6, and n3 represents an integer from 1 to 4.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and a resin sheet, a prepreg, and a printed wiring board each using the resin composition. [Background technology]

[0002] In recent years, printed wiring boards, which are widely used in electronic devices, communication devices, personal computers, etc., have become increasingly dense, highly integrated, and lighter and thinner. Accordingly, the insulating layer of a printed wiring board is required to have a lower dielectric constant, a lower dielectric tangent, and a thinner film, and various studies have been conducted on resin compositions used for insulating layers. For example, Patent Document 1 describes a resin composition containing a maleimide compound (A), a cyanate ester compound (F), a polyphenylene ether compound (B) having a specific structure and a number average molecular weight of 1000 to 7000, and a block copolymer (C) having a styrene skeleton. This resin composition can simultaneously achieve low dielectric constant, low dielectric tangent, and low thermal expansion, and can obtain a uniform cured product. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2019 / 230945 Summary of the Invention [Problem to be solved by the invention]

[0004] However, in conventional printed wiring boards, for example, prepregs in which glass fibers are impregnated with resin are often used as insulating layers. The resin composition described in Patent Document 1 is also suitable for prepregs. Although prepregs contain glass fibers and can obtain a certain strength, their thickness cannot be made thinner than that of glass fibers. Therefore, there was a problem that they are insufficient to meet the recent trend toward thinner films. In addition, in the case of prepregs, the dielectric constant and dielectric loss tangent of glass fibers and resin are different, so that the characteristics of the insulating layer become uneven, and further reduction in the dielectric constant and dielectric loss tangent is difficult because the dielectric constant and dielectric loss tangent of glass fibers are larger than those of resins. Furthermore, in the recent trend toward higher frequencies of electric signals, there was also a problem that if the dielectric constant of the insulating layer is unstable due to the skin effect, high-frequency signal loss increases, making it difficult to obtain sufficient characteristics.

[0005] Furthermore, if an insulating layer is formed from a resin without using glass fibers, it is possible to achieve a thinner film, a lower dielectric constant, a lower dielectric tangent, and lower high-frequency signal loss. However, conventional resin compositions cannot provide sufficient flexibility, which can lead to problems such as molding defects and inability to obtain sufficient peel strength.

[0006] The present invention has been made in view of the above problems, and a first object of the present invention is to provide a resin composition which can provide excellent low dielectric constant, low dielectric tangent, flexibility, and peel strength, can be thinned, and can reduce high-frequency signal loss, and a resin sheet and a printed wiring board which use the resin composition.

[0007] A second object is to provide a prepreg which is capable of achieving excellent moldability, low dielectric constant, low dielectric tangent, and peel strength. [Means for solving the problem]

[0008] The present inventors have found that the above-mentioned problems can be solved by a resin composition that combines a maleimide compound (A) that has an aromatic ring in its main skeleton and that exhibits a relative dielectric constant at 10 GHz of less than 2.7 when cured alone, a specific polyphenylene ether compound (B), and a block copolymer (C) having a styrene skeleton, and have completed the present invention.

[0009] That is, the present invention is as follows. [1] A resin composition comprising: a maleimide compound (A) having an aromatic ring in its main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone; a polyphenylene ether compound (B) represented by the following general formula (1) and having a number average molecular weight of 1000 or more and 7000 or less; and a block copolymer (C) having a styrene skeleton. [ka] (In the above general formula (1), X represents an aryl group, -(Y-O)n2- represents a polyphenylene ether moiety, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer of 1 to 100, n1 represents an integer of 1 to 6, and n3 represents an integer of 1 to 4.) [2] The resin composition according to [1], wherein the maleimide compound (A) is at least one selected from the group consisting of a compound represented by the following general formula (6) and a compound represented by the following general formula (22): [ka] (In the above general formula (6), n6 represents an integer of 1 or more.) [ka] (In the above general formula (22), R M1 , R M2 , R M3 , and R M4 R each independently represents a hydrogen atom or an organic group. M5 and R M6Each independently represents a hydrogen atom or an alkyl group. M represents a divalent aromatic group. A is a 4- to 6-membered alicyclic group. R M7 and R M8 are each independently an alkyl group. mx is 1 or 2, and lx is 0 or 1. R M9 and R M10 Each independently represents a hydrogen atom or an alkyl group. M11 , R M12 , R M13 , and R M14 Each independently represents a hydrogen atom or an organic group. nx represents an integer of 0 or more and 20 or less. [3] The resin composition according to [1], wherein the block copolymer (C) having a styrene skeleton contains at least one selected from the group consisting of a styrene-butadiene block copolymer, a styrene-isoprene block copolymer, a styrene-hydrogenated butadiene block copolymer, a styrene-hydrogenated isoprene copolymer, and a styrene-hydrogenated (isoprene / butadiene) copolymer. [4] The resin composition according to [1], further comprising a maleimide compound (D) other than the maleimide compound (A). [5] The resin composition according to [4], wherein the maleimide compound (D) contains at least one selected from the group consisting of the following general formulas (2), (3), (4) and (5): [ka] (In the above general formula (2), R 41 ,R 42 Each independently represents a hydrogen atom or a methyl group, and n4 represents an integer of 1 or more. [ka] (In the above general formula (3), R 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R 506 ,R507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512 each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or a phenyl group, and n5 represents an integer of 1 or more and 10 or less. [ka] (In the above general formula (4), R 61 ,R 62 ,R 63 ,R 64 each independently represents a hydrogen atom, a methyl group, or an ethyl group; R 71 ,R 72 each independently represents a hydrogen atom or a methyl group. [ka] (In the above general formula (5), R 81 ,R 82 each independently represents a hydrogen atom, a methyl group, or an ethyl group. [6] The resin composition according to [1], further comprising a flame retardant (E). [7] The resin composition according to [1], further comprising a cyanate ester compound (F). [8] A resin sheet comprising a support and a layer formed from the resin composition according to [1] disposed on a surface of the support. [9] A prepreg comprising a substrate and the resin composition according to [1] impregnated into or applied to the substrate.

[10] A printed wiring board comprising an insulating layer and a conductor layer disposed on a surface of the insulating layer, the insulating layer comprising a layer formed from the resin composition according to [1]. Effect of the Invention

[0010] The resin composition, resin sheet, and printed wiring board of the present invention can provide excellent low dielectric constant, low dielectric loss tangent, flexibility, and peel strength, can be made thin, and can reduce high-frequency signal loss. In addition, in the case of a prepreg, excellent moldability, low dielectric constant, low dielectric loss tangent, and peel strength can be obtained. Therefore, the industrial practical use is extremely high. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Below, we will explain in detail the form for implementing the present invention (hereinafter referred to as the "present embodiment"). However, the present invention is not limited to this, and various modifications are possible without departing from the gist of the present invention.

[0012] [Resin composition] The resin composition according to the present embodiment contains a maleimide compound (A) having an aromatic ring in its main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) represented by the following general formula (1) and having a number average molecular weight of 1000 or more and 7000 or less, and a block copolymer (C) having a styrene skeleton. [ka] (In the above general formula (1), X represents an aryl group, -(Y-O)n2- represents a polyphenylene ether moiety, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer of 1 to 100, n1 represents an integer of 1 to 6, and n3 represents an integer of 1 to 4.)

[0013] [Maleimide compound (A)] The maleimide compound (A) according to the present embodiment is a compound having one or more maleimide groups in the molecule, and when cured alone, it exhibits a relative dielectric constant at 10 GHz of less than 2.7. The resin composition according to the present embodiment contains the maleimide compound (A), and thus has excellent low dielectric constant, low dielectric loss tangent, and peel strength. As the maleimide compound (A), it is preferable to contain at least one selected from the group consisting of compounds represented by the following general formula (6) and compounds represented by the following general formula (22). [ka] In the general formula (6), n6 represents an integer of 1 or more. The compound (A) represented by the general formula (6) may contain two or more compounds having different n6. [ka] (In the above general formula (22), R M1 , R M2 , R M3 , and R M4 R each independently represents a hydrogen atom or an organic group. M5 and R M6 Each independently represents a hydrogen atom or an alkyl group. M represents a divalent aromatic group. A is a 4- to 6-membered alicyclic group. R M7 and R M8 are each independently an alkyl group. mx is 1 or 2, and lx is 0 or 1. R M9 and R M10 Each independently represents a hydrogen atom or an alkyl group. M11 , R M12 , R M13 , and R M14 Each independently represents a hydrogen atom or an organic group. nx represents an integer of 0 or more and 20 or less. The compound (A) represented by the general formula (22) may contain two or more compounds having different nx.

[0014] R in general formula (22) M1 , R M2, R M3 , and R M4 R each independently represents a hydrogen atom or an organic group. The organic group is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, even more preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M1 and R M3 are each independently preferably an alkyl group, and R M2 and R M4 is preferably a hydrogen atom. R M5 and R M6 each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group here is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and among these, a methyl group is particularly preferred. Ar M represents a divalent aromatic group, preferably a phenylene group, a naphthalenediyl group, a phenanthrenediyl group, or an anthracenediyl group, more preferably a phenylene group, and further preferably an m-phenylene group. M may have a substituent, and the substituent is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, even more preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M is preferably unsubstituted. A is a 4- to 6-membered alicyclic group, and more preferably a 5-membered alicyclic group (preferably a group which forms an indan ring when combined with a benzene ring). M7 and R M8 are each independently an alkyl group, preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and particularly preferably a methyl group. mx is 1 or 2, and preferably 2. lx is 0 or 1, and preferably 1. R M9 and R M10each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group here is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and among these, a methyl group is particularly preferred. R M11 , R M12 , R M13 , and R M14 R each independently represents a hydrogen atom or an organic group. The organic group is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, even more preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M12 and R M13 are each independently preferably an alkyl group, and R M11 and R M14 is preferably a hydrogen atom. nx represents an integer of 0 or more and 20 or less. nx may be an integer of 10 or less. When the resin composition of the present embodiment contains a maleimide compound (A) represented by general formula (22) and a compound in which nx is 0, in addition to the compound in which nx is 0, it contains at least one compound other than the compound in which nx is 0, but it may contain two or more compounds other than the compound in which nx is 0. When it does not contain a compound in which nx is 0, it may contain only one compound with at least a different nx value, or it may contain two or more compounds with different values. When two or more kinds are contained, the average value of nx (average number of repeating units) n in the maleimide compound (A) represented by general formula (22) in the resin composition is preferably 0.95 or more, more preferably 0.98 or more, even more preferably 1.0 or more, and even more preferably 1.1 or more, in order to obtain a low melting point (low softening point), low melt viscosity, and excellent handleability, and is preferably 10.0 or less, more preferably 8.0 or less, even more preferably 7.0 or less, and even more preferably 6.0 or less. The same applies to formula (26) and formula (27) described later.

[0015] The compound represented by the general formula (22) is preferably a compound represented by the following general formula (26). [ka] (In general formula (26), R M21 , R M22 , R M23 , and R M24 R each independently represents a hydrogen atom or an organic group. M25 and R M26 Each independently represents a hydrogen atom or an alkyl group. M27 , R M28 , R M29 , and R M30 R each independently represents a hydrogen atom or an organic group. M31 and R M32 Each independently represents a hydrogen atom or an alkyl group. M33 , R M34 , R M35 , and R M36 R each independently represents a hydrogen atom or an organic group. M37 , R M38 , R M39 Each independently represents a hydrogen atom or an alkyl group. nx represents an integer of 0 or more and 20 or less.

[0016] R in general formula (26) M21 , R M22 , R M23 , and R M24 R each independently represents a hydrogen atom or an organic group. The organic group is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, even more preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. M21 and R M23 is preferably an alkyl group, R M22 and R M24 is preferably a hydrogen atom. R M25 and R M26each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group here is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and among these, a methyl group is particularly preferred. R M27 , R M28 , R M29 , and R M30 each independently represents a hydrogen atom or an organic group, preferably a hydrogen atom. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. R M31 and R M32 each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group here is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and among these, a methyl group is particularly preferred. R M33 , R M34 , R M35 , and R M36 each independently represents a hydrogen atom or an organic group. The organic group here is preferably an alkyl group, more preferably an alkyl group having 1 to 12 carbon atoms, still more preferably an alkyl group having 1 to 6 carbon atoms, still more preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and particularly preferably a methyl group. R M33 and R M36 is preferably a hydrogen atom, R M34 and R M35 is preferably an alkyl group. R M37 , R M38 , R M39each independently represents a hydrogen atom or an alkyl group, preferably an alkyl group. The alkyl group here is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, further preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and among these, a methyl group is particularly preferred. nx represents an integer of 0 to 20. nx may be an integer of 10 or less.

[0017] The compound represented by the general formula (26) is preferably a compound represented by the following general formula (27). [ka] (In the general formula (27), nx represents an integer of 0 or more and 20 or less.)

[0018] The molecular weight of the compound (A) represented by the general formula (22) is preferably 500 or more, more preferably 600 or more, and even more preferably 700 or more. By making it equal to or more than the lower limit, the dielectric properties (low dielectric property) and low water absorption tend to be improved. In addition, the molecular weight of the compound (A) represented by the general formula (22) is preferably 10000 or less, more preferably 9000 or less, even more preferably 7000 or less, even more preferably 5000 or less, and even more preferably 4000 or less. By making it equal to or less than the upper limit, the heat resistance and handling property tend to be improved.

[0019] In addition, the compound (A) represented by general formula (22) used in this embodiment preferably has high heat resistance in its cured product. The cured product of the compound (A) represented by general formula (22) used in this embodiment preferably has a glass transition temperature of 180°C or higher, more preferably 200°C or higher, and even more preferably 230°C or higher, measured according to JIS C6481 dynamic viscoelasticity measurement. By setting the glass transition temperature to the lower limit or higher, a cured product with better heat resistance can be obtained. In addition, it is practical for the upper limit of the glass transition temperature to be 400°C or lower. In addition, the compound (A) used in this embodiment and represented by the general formula (22) preferably has excellent dielectric properties when cured. For example, the cured product of the compound (A) used in this embodiment and represented by the general formula (22) preferably has a relative dielectric constant of less than 2.7 at 10 GHz measured according to the cavity resonance perturbation method, and more preferably has a relative dielectric constant of 2.6 or less. In addition, the lower limit of the dielectric constant is, for example, 2.0 or more in practical use. In addition, the cured product of the compound (A) used in this embodiment and represented by the formula (22) preferably has a relative dielectric tangent (Df) of 0.01 or less at 10 GHz measured according to the cavity resonance perturbation method, and more preferably has a relative dielectric tangent of 0.007 or less. In addition, the lower limit of the dielectric tangent is, for example, 0.0001 or more in practical use.

[0020] In addition, in the resin composition of this embodiment, the content of the compound (A) represented by the general formula (22) is preferably 1% by mass or more, more preferably 5% by mass or more, based on the total amount of the resin solid content. By making it equal to or more than the lower limit, the heat resistance tends to be further improved. In addition, the upper limit of the content of the compound (A) represented by the general formula (22) is preferably 90% by mass or less, more preferably 60% by mass or less, even more preferably 40% by mass or less, and may be 30% by mass or less, based on the resin solid content in the resin composition. By making it equal to or less than the upper limit, the low water absorbency tends to be further improved. The resin composition of the present embodiment may contain only one type of compound (A) represented by general formula (22), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0021] The maleimide compound (A) used in this embodiment may be a commercially available product. For example, the maleimide compound represented by the general formula (6) may be "MIR-5000" manufactured by Nippon Kayaku Co., Ltd. For example, the maleimide compound represented by the general formula (22) may be "X9-450" or "X9-470" manufactured by DIC Corporation.

[0022] The content of the maleimide compound (A) in the resin composition according to the present embodiment is preferably 1 part by mass or more, and more preferably 5 parts by mass or more, as a lower limit, when the resin solid content in the resin composition is 100 parts by mass. The upper limit is preferably 90 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 40 parts by mass or less, and may be 30 parts by mass or less. By setting it in such a range, there is a tendency to effectively achieve low dielectric constant, low dielectric loss tangent, and good flexibility.

[0023] Only one maleimide compound (A) may be used, or two or more may be used. When two or more are used, the total amount is preferably within the above range. Here, the "resin solid content in the resin composition" refers to the components in the resin composition excluding the solvent, unless otherwise specified, and 100 parts by mass of the resin solid content refers to the total amount of the components in the resin composition excluding the solvent being 100 parts by mass.

[0024] [Polyphenylene ether compound (B)] The polyphenylene ether compound (B) according to the present embodiment is a compound represented by general formula (1). The resin composition according to the present embodiment contains the polyphenylene ether compound (B) having such a structure, and thus excellent low dielectric constant and low dielectric loss tangent can be obtained, and a uniform cured product can be obtained. In addition, in the present embodiment, by using the maleimide compound (A) represented by general formula (22) in combination with the polyphenylene ether compound (B), it is possible to achieve more excellent dielectric properties than when the maleimide compound and the polyphenylene ether compound (B) used in the past are used in combination. The polyphenylene ether compound (B) represented by general formula (1) used in the present embodiment has a number average molecular weight of 1000 or more and 7000 or less. By setting the number average molecular weight to 7000 or less, it is possible to ensure the flowability during molding. In addition, by setting the number average molecular weight to 1000 or more, it is possible to obtain the excellent dielectric properties (low dielectric constant, low dielectric loss tangent) and heat resistance inherent to the polyphenylene ether resin. Among these, in order to obtain better fluidity, heat resistance, and dielectric properties, it is preferable that the number average molecular weight of the polyphenylene ether compound (B) is 1100 or more and 5000 or less. More preferably, the number average molecular weight of the polyphenylene ether compound (B) is 4500 or less, and even more preferably, the number average molecular weight of the polyphenylene ether compound (B) is 3000 or less. The number average molecular weight is measured by gel permeation chromatography according to a standard method.

[0025] The polyphenylene ether compound (B) represented by the general formula (1) used in this embodiment preferably has a minimum melt viscosity of 50,000 Pa·s or less. By setting the minimum melt viscosity to 50,000 Pa·s or less, fluidity can be ensured and multi-layer molding becomes possible. The lower limit of the minimum melt viscosity is not particularly set, but may be, for example, 1,000 Pa·s or more.

[0026] The polyphenylene ether compound (B) represented by general formula (1) preferably contains a polymer of a structural unit represented by the following general formula (7). [ka] (In general formula (7), R 901 ,R 902 ,R 903 ,R 904 may be the same or different and represent an alkyl group having 6 or less carbon atoms, an aryl group, a halogen atom, or a hydrogen atom.

[0027] The polymer may further contain at least one structural unit selected from the group consisting of structural units represented by general formula (8) and general formula (9). [ka] (In general formula (8), R 905 ,R 906 ,R 907 ,R 911 ,R 912 R may be the same or different and represents an alkyl group having 6 or less carbon atoms or a phenyl group. 908 ,R 909 ,R 910 each independently represents a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group. [ka] (In general formula (9), R 913 ,R 914 ,R 915 ,R 916 ,R 917 ,R 918 ,R 919 ,R 920 may be the same or different and represent a hydrogen atom, an alkyl group having 6 or less carbon atoms, or a phenyl group. -A- represents a linear, branched, or cyclic divalent hydrocarbon group having 20 or less carbon atoms. In terms of the relationship with general formula (1), the above general formulae (8), (9) and (10) are preferably -(YO)- in general formula (1), where -(YO)- has a repeating unit with n2 being the number (1 to 100).

[0028] In the general formula (1), X represents an aryl group (aromatic group), -(YO)n2- represents a polyphenylene ether moiety, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer of 1 to 100, n1 represents an integer of 1 to 6, and n3 represents an integer of 1 to 4. Preferably, n1 is an integer of 1 to 4, more preferably, n1 is 1 or 2, and ideally, n1 is 1. Also, preferably, n3 is an integer of 1 to 3, more preferably, n3 is 1 or 2, and ideally, n3 is 2.

[0029] An aromatic hydrocarbon group can be used as the aryl group in X of the general formula (1). Specifically, a group obtained by removing n3 hydrogen atoms from one ring structure selected from a benzene ring structure, a biphenyl structure, an indenyl ring structure, and a naphthalene ring structure (for example, a phenyl group, a biphenyl group, an indenyl group, and a naphthyl group) can be used, and preferably a biphenyl group is used. Here, the aryl group may include a diphenyl ether group in which the above-mentioned aryl group is bonded via an oxygen atom, a benzophenone group in which the aryl group is bonded via a carbonyl group, and a 2,2-diphenylpropane group in which the aryl group is bonded via an alkylene group. In addition, the aryl group may be substituted with a general substituent such as an alkyl group (preferably an alkyl group having 1 to 6 carbon atoms, particularly a methyl group), an alkenyl group, an alkynyl group, or a halogen atom. However, since the "aryl group" is substituted on the polyphenylene ether moiety via an oxygen atom, the limit of the number of general substituents depends on the number of polyphenylene ether moieties.

[0030] It is particularly preferable that the polyphenylene ether compound (B) contains a polyphenylene ether represented by the structure of the following general formula (10). [ka] (In the general formula (10), X is an aryl group (aromatic group), -(YO)n2- each represents a polyphenylene ether moiety, and n2 each represents an integer of 1 to 100.) -(YO)n2- and n2 have the same meanings as in the general formula (1). A plurality of compounds having different n2 may be included.

[0031] X in general formula (1) and general formula (10) is preferably general formula (11), general formula (12), or general formula (13), and -(YO)- in general formula (1) and general formula (10) is more preferably a structure in which general formula (14) or general formula (15) is arranged, or a structure in which general formula (14) and general formula (15) are arranged randomly. [ka] [ka] (In general formula (12), R 921 ,R 922 ,R 923 ,R 924 each independently represents a hydrogen atom or a methyl group; -B- is a linear, branched or cyclic divalent hydrocarbon group having 20 or less carbon atoms. [ka] (In general formula (13), -B- is a linear, branched or cyclic divalent hydrocarbon group having 20 or less carbon atoms.) [ka] [ka]

[0032] The method for producing the modified polyphenylene ether having the structure represented by general formula (10) is not particularly limited, and the modified polyphenylene ether can be produced, for example, by subjecting a terminal phenolic hydroxyl group of a bifunctional phenylene ether oligomer obtained by oxidative coupling of a bifunctional phenol compound and a monofunctional phenol compound to vinylbenzyl etherification. Moreover, as such modified polyphenylene ether, commercially available products can be used. For example, OPE-2St1200 and OPE-2st2200 manufactured by Mitsubishi Gas Chemical Co., Inc. can be suitably used.

[0033] The content of the polyphenylene ether compound (B) in the resin composition according to the present embodiment is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, based on 100 parts by mass of the resin solid content of the resin composition. The upper limit of the content is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, and may be 25 parts by mass or less. By setting the content in this range, there is a tendency to effectively achieve low dielectric constant, low dielectric loss tangent, and good moldability. The resin composition may contain only one type of polyphenylene ether compound (B), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0034] [Block copolymer with styrene skeleton (C)] The "block copolymer (C) having a styrene skeleton" according to the present embodiment refers to an elastomer that is a block copolymer having a polystyrene block structure, and does not include random copolymers. In addition, compounds consisting only of aromatic vinyl compounds are not included in the "block copolymer (C) having a styrene skeleton." The resin composition according to the present embodiment can obtain excellent low dielectric constant, low dielectric loss tangent, and flexibility by containing the block copolymer (C) having a styrene skeleton.

[0035] The block copolymer (C) having a styrene skeleton used in the resin composition according to the present embodiment preferably contains at least one selected from the group consisting of styrene-butadiene block copolymers, styrene-isoprene block copolymers, styrene-hydrogenated butadiene block copolymers, styrene-hydrogenated isoprene block copolymers, and styrene-hydrogenated (isoprene / butadiene) block copolymers. These block copolymers may be used alone or in combination of two or more. In particular, styrene-isoprene block copolymers, styrene-hydrogenated butadiene block copolymers, styrene-hydrogenated isoprene block copolymers, and styrene-hydrogenated (butadiene / isoprene) block copolymers are preferred because they provide a more excellent low dielectric tangent.

[0036] In the present embodiment, the polystyrene block structure may be one having a substituent, such as styrene derivatives including α-methylstyrene, 3-methylstyrene, 4-propylstyrene, and 4-cyclohexylstyrene.

[0037] The styrene content in the block copolymer (C) having a styrene skeleton (hereinafter also referred to as "styrene ratio") is not particularly limited, but is preferably 10% by mass or more, more preferably 20% by mass or more. The upper limit of the styrene content is not particularly limited as long as it is less than 100% by mass, but is preferably less than 99% by mass, and more preferably 70% by mass or less. By setting it in such a range, the solvent solubility and compatibility with other compounds tend to be further improved. Here, the styrene content is a value expressed by (a) / (b)×100 (unit: %), where the mass of the styrene unit contained in the block copolymer (C) having a styrene skeleton is (a) g, and the mass of the entire block copolymer (C) having a styrene skeleton is (b) g.

[0038] The content of the block copolymer (C) having a styrene skeleton in the resin composition according to the present embodiment is preferably 1 part by mass or more, preferably 5 parts by mass or more, and may be 8 parts by mass or more, based on 100 parts by mass of the resin solid content of the resin composition. The upper limit of the content is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 22 parts by mass or less. By setting the content in such a range, the resin composition tends to have a lower dielectric constant, a lower dielectric loss tangent, and excellent moldability. The resin composition may contain only one type of block copolymer (C) having a styrene skeleton, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0039] As the block copolymer (C) having a styrene skeleton in this embodiment, a commercially available product may be used. For example, styrene-butadiene-styrene block copolymers include TR2630 (manufactured by JSR Corporation) and TR2003 (manufactured by JSR Corporation). In addition, styrene-isoprene-styrene block copolymers include SIS5250 (manufactured by JSR Corporation). Styrene-hydrogenated isoprene-styrene block copolymers include SEPTON2104 (manufactured by Kuraray Co., Ltd.).

[0040] [Maleimide compound (D)] The resin composition according to the present embodiment preferably further contains a maleimide compound (D) other than the maleimide compound (A). As the maleimide compound (D), for example, it is preferable to contain at least one selected from the group consisting of the following general formulas (2), (3), (4) and (5). This is because low thermal expansion and heat resistance can be improved. Note that the [maleimide compound (D)] used in the present embodiment is not included in the above-mentioned [maleimide compound (A)] and is distinguished from it.

[0041] [ka] In general formula (2), R 41 ,R 42each independently represents a hydrogen atom or a methyl group, and is preferably a hydrogen atom. In addition, in the general formula (2), n4 represents an integer of 1 or more, and the upper limit of n4 is usually 10, and from the viewpoint of solubility in an organic solvent, the upper limit of n4 is preferably 7, and more preferably 5. The compound represented by the general formula (2) may contain two or more compounds having different n4.

[0042] [ka] In general formula (3), R 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R 506 ,R 507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512 each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms (e.g., a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, etc.), or a phenyl group. Among these, from the viewpoint of improving flame resistance and metal foil (copper foil) peel strength, a group selected from the group consisting of a hydrogen atom, a methyl group, and a phenyl group is preferred, one of a hydrogen atom and a methyl group is more preferred, and a hydrogen atom is even more preferred. In general formula (3), n5 is an integer satisfying 1≦n5≦10. From the viewpoint of achieving even better solvent solubility, n5 is preferably 4 or less, more preferably 3 or less, and even more preferably 2 or less. The compound represented by general formula (3) may contain two or more compounds having different n5.

[0043] [ka] In the above general formula (4), R 61 ,R 62 ,R 63 ,R 64 each independently represents a hydrogen atom, a methyl group, or an ethyl group; R71 ,R 72 Each independently represents a hydrogen atom or a methyl group. From the viewpoint of further excellent low dielectric constant and low dielectric tangent, R 61 ,R 62 ,R 63 ,R 64 is preferably a methyl group or an ethyl group. An example of such a compound is 3,3'-diethyl-5,5'-dimethyl-4,4'-diphenylmethane bismaleimide.

[0044] [ka] In general formula (5), R 81 ,R 82 Each independently represents a hydrogen atom, a methyl group, or an ethyl group. From the viewpoint of even more excellent low dielectric constant and low dielectric tangent, R 81 ,R 82 is preferably a methyl group. An example of such a compound is 2,2-bis(4-(4-maleimidophenoxy)-phenyl)propane.

[0045] The maleimide compound (D) used in this embodiment may be a commercially available product. For example, "BMI-2300" manufactured by Daiwa Kasei Kogyo Co., Ltd. is a maleimide compound represented by general formula (2), "MIR-3000" manufactured by Nippon Kayaku Co., Ltd. is a maleimide compound represented by general formula (3), "BMI-70" manufactured by K.I. Kasei Co., Ltd. is a maleimide compound represented by general formula (4), and "BMI-80" manufactured by K.I. Kasei Co., Ltd. is a maleimide compound represented by general formula (5).

[0046] The content of the maleimide compound (D) in the resin composition according to the present embodiment can be appropriately set according to the desired properties, and is not particularly limited. When the maleimide compound (D) is contained, the content is preferably 1 part by mass or more, and more preferably 5 parts by mass or more, when the resin solid content in the resin composition is 100 parts by mass. The upper limit is preferably 90 parts by mass or less, more preferably 60 parts by mass or less, further preferably 40 parts by mass or less, and may be 30 parts by mass or less. By setting it in such a range, high heat resistance and low water absorption tend to be more effectively exhibited. The maleimide compound (D) may be used alone or in combination of two or more. When two or more types are used, the total amount is preferably within the above range.

[0047] [Flame retardant (E)] The resin composition according to the present embodiment preferably contains a flame retardant (E) to improve flame resistance. As the flame retardant (E) used in the present embodiment, known flame retardants can be used, for example, halogen-based flame retardants such as brominated epoxy resin, brominated polycarbonate, brominated polystyrene, brominated styrene, brominated phthalimide, tetrabromobisphenol A, pentabromobenzyl (meth)acrylate, pentabromotoluene, tribromophenol, hexabromobenzene, decabromodiphenyl ether, bis-1,2-pentabromophenylethane, chlorinated polystyrene, and chlorinated paraffin, red phosphorus, tricresyl phosphate, triphenyl phosphate, and cresyl diphenyl phosphate. Examples of the flame retardant include phosphorus-based flame retardants such as phenyl phosphate, trixylenyl phosphate, trialkyl phosphate, dialkyl phosphate, tris(chloroethyl)phosphate, phosphazene, 1,3-phenylenebis(2,6-dixylenyl phosphate), 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide, inorganic flame retardants such as aluminum hydroxide, magnesium hydroxide, partial boehmite, boehmite, zinc borate, and antimony trioxide, and silicone-based flame retardants such as silicone rubber and silicone resin. These flame retardants may be used alone or in combination of two or more. Among these, phosphorus-based flame retardants are preferred, and in particular, 1,3-phenylenebis(2,6-dixylenyl phosphate) is preferred because it is less likely to impair low dielectric properties. The phosphorus content in the resin composition is preferably 0.1% by mass to 5% by mass.

[0048] The content of the flame retardant (E), when contained, is preferably 1 part by mass or more, more preferably 5 parts by mass or more, based on 100 parts by mass of the resin solid content in the resin composition. The upper limit of the content is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and may be 15 parts by mass or less. Only one type of flame retardant (E) may be used, or two or more types may be used. When two or more types are used, the total amount is preferably within the above range.

[0049] [Cyanate ester compounds (F)] The cyanate ester compound (F) according to this embodiment is not particularly limited as long as it is a resin having an aromatic moiety in the molecule substituted with at least one cyanato group (cyanate ester group). An example of the cyanate ester compound (F) in this embodiment is a compound represented by general formula (23).

[0050] [ka] In the general formula (23), Ar1 and Ar2 each independently represent a phenylene group which may have a substituent, a naphthylene group which may have a substituent, or a biphenylene group which may have a substituent. 101 ,R 102 are each independently selected from any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may have a substituent, an aryl group having 6 to 12 carbon atoms which may have a substituent, an alkoxy group having 1 to 4 carbon atoms which may have a substituent, an aralkyl group which is formed by bonding an alkyl group having 1 to 6 carbon atoms and an aryl group having 6 to 12 carbon atoms which may have a substituent, and an alkylaryl group which is formed by bonding an alkyl group having 1 to 6 carbon atoms and an aryl group having 6 to 12 carbon atoms which may have a substituent. 81 represents the number of cyanato groups bonded to Ar1 and is an integer of 1 to 3. 82 represents the number of cyanato groups bonded to Ar2 and is an integer of 1 to 3. 83 is R bonded to Ar1 101 When Ar1 is a phenylene group, it is 4-n 81 , 6-n for naphthylene group 81 , 8-n for biphenylene group 81 n 84 is R bonded to Ar2 102 When Ar2 is a phenylene group, it is 4-n 82 , 6-n for naphthylene group 82 , 8-n for biphenylene group 82 n 85 represents the average number of repetitions and is an integer of 0 to 50. The cyanate ester compound (F) is 85Each Z is independently selected from a single bond, a divalent organic group having 1 to 50 carbon atoms (hydrogen atoms may be substituted with heteroatoms), a divalent organic group having 1 to 10 nitrogen atoms (such as -NRN-), a carbonyl group (-CO-), a carboxy group (-C(=O)O-), a carbonyl dioxide group (-OC(=O)O-), a sulfonyl group (-SO2-), and a divalent sulfur atom or a divalent oxygen atom.

[0051] R in general formula (23) 101 ,R 102 The alkyl group in the general formula (23) may have a linear structure, a branched structure, or a cyclic structure (such as a cycloalkyl group). 101 ,R 102 A hydrogen atom in the aryl group in the formula (I) may be substituted with a halogen atom such as a fluorine atom or a chlorine atom, an alkoxy group such as a methoxy group or a phenoxy group, a cyano group, or the like. Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-pentyl group, a 1-ethylpropyl group, a 2,2-dimethylpropyl group, a cyclopentyl group, a hexyl group, a cyclohexyl group, and a trifluoromethyl group. Specific examples of the aryl group include a phenyl group, a xylyl group, a mesityl group, a naphthyl group, a phenoxyphenyl group, an ethylphenyl group, an o-, m- or p-fluorophenyl group, a dichlorophenyl group, a dicyanophenyl group, a trifluorophenyl group, a methoxyphenyl group, and an o-, m- or p-tolyl group. Specific examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, an n-butoxy group, an isobutoxy group, and a tert-butoxy group. Specific examples of the divalent organic group in Z of the general formula (23) include a methylene group, an ethylene group, a trimethylene group, a cyclopentylene group, a cyclohexylene group, a trimethylcyclohexylene group, a biphenylylmethylene group, a dimethylmethylene-phenylene-dimethylmethylene group, a fluorenediyl group, and a phthalidodiyl group. The hydrogen atom in the divalent organic group may be substituted with a halogen atom such as a fluorine atom or a chlorine atom, an alkoxy group such as a methoxy group or a phenoxy group, or a cyano group. Examples of the divalent organic group having 1 to 10 nitrogen atoms in Z of the general formula (23) include an imino group and a polyimide group.

[0052] Furthermore, Z in the general formula (23) may be a structure represented by the following general formula (24) or the following general formula (25). [ka] In the general formula (24), Ar3 is selected from any one of a phenylene group, a naphthylene group, and a biphenylene group. 103 ,R 104 ,R 107 ,R 108 are each independently selected from any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aryl group substituted with at least one of a trifluoromethyl group and a phenolic hydroxy group. 105 ,R 106 are each independently selected from any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, and a hydroxy group. 86 represents an integer of 0 to 5, and the cyanate ester compound (F) has n 86 may be a mixture of compounds having different groups.) [ka] In the general formula (25), Ar4 is selected from any one of a phenylene group, a naphthylene group, and a biphenylene group. 109 ,R 110are each independently selected from any one of a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a benzyl group, an alkoxy group having 1 to 4 carbon atoms, and an aryl group substituted with at least one of a hydroxyl group, a trifluoromethyl group, and a cyanato group. 87 represents an integer of 0 to 5, and the cyanate ester compound (F) has n 87 may be a mixture of compounds having different groups.)

[0053] Furthermore, Z in the general formula (23) may be a divalent group represented by the following formula: [ka] (In the formula, n 88 represents an integer from 4 to 7. 111 ,R 112 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. Specific examples of Ar3 in the general formula (24) and Ar4 in the general formula (25) include a 1,4-phenylene group, a 1,3-phenylene group, a 4,4'-biphenylene group, a 2,4'-biphenylene group, a 2,2'-biphenylene group, a 2,3'-biphenylene group, a 3,3'-biphenylene group, a 3,4'-biphenylene group, a 2,6-naphthylene group, a 1,5-naphthylene group, a 1,6-naphthylene group, a 1,8-naphthylene group, a 1,3-naphthylene group, and a 1,4-naphthylene group. 103 ~R 108 and R in the general formula (25) 109 ,R 110 The alkyl group and aryl group in the formula (23) are the same as those described above.

[0054] Examples of the cyanate ester compound represented by general formula (23) include a phenol novolac type cyanate ester compound, a naphthol aralkyl type cyanate ester compound, a biphenyl aralkyl type cyanate ester compound, a naphthylene ether type cyanate ester compound, a xylene resin type cyanate ester compound, an adamantane skeleton type cyanate ester compound, a bisphenol A type cyanate ester compound, a diallyl bisphenol A type cyanate ester compound, and a naphthol aralkyl type cyanate ester compound.

[0055] Specific examples of the cyanate ester compound represented by the general formula (23) include cyanatobenzene, 1-cyanato-2-, 1-cyanato-3-, or 1-cyanato-4-methylbenzene, 1-cyanato-2-, 1-cyanato-3-, or 1-cyanato-4-methoxybenzene, 1-cyanato-2,3-, 1-cyanato-2,4-, 1-cyanato-2,5-, 1-cyanato-2,6-, 1-cyanato-3,4-, or 1-cyanato-3,5-dimethylbenzene, cyanatoethylbenzene, cyanatobutylbenzene, cyanatooctylbenzene, and cyanatononylbenzene. , 2-(4-cyanaphenyl)-2-phenylpropane (cyanate of 4-α-cumylphenol), 1-cyanato-4-cyclohexylbenzene, 1-cyanato-4-vinylbenzene, 1-cyanato-2- or 1-cyanato-3-chlorobenzene, 1-cyanato-2,6-dichlorobenzene, 1-cyanato-2-methyl-3-chlorobenzene, cyanatonitrobenzene, 1-cyanato-4-nitro-2-ethylbenzene, 1-cyanato-2-methoxy-4-allylbenzene (cyanate of eugenol), methyl(4-cyanatophenyl)sulfide 1-cyanato-3-trifluoromethylbenzene, 4-cyanatobiphenyl, 1-cyanato-2- or 1-cyanato-4-acetylbenzene, 4-cyanatobenzaldehyde, 4-cyanatobenzoic acid methyl ester, 4-cyanatobenzoic acid phenyl ester, 1-cyanato-4-acetaminobenzene, 4-cyanatobenzophenone, 1-cyanato-2,6-di-tert-butylbenzene, 1,2-dicyanatobenzene, 1,3-dicyanatobenzene, 1,4-dicyanatobenzene, 1,4-dicyanato-2-tert-butylbenzene, 1,4 -dicyanato-2,4-dimethylbenzene, 1,4-dicyanato-2,3,4-dimethylbenzene, 1,3-dicyanato-2,4,6-trimethylbenzene, 1,3-dicyanato-5-methylbenzene, 1-cyanato or 2-cyanatonaphthalene, 1-cyanato-4-methoxynaphthalene, 2-cyanato-6-methylnaphthalene, 2-cyanato-7-methoxynaphthalene, 2,2'-dicyanato-1,1'-binaphthyl, 1,3-, 1,4-, 1,5-, 1,6-, 1,7-, 2,3-, 2,6- or 2,7-dicyanatosinaphthalene, 2,2'- or 4,4'-dicyanatobiphenyl, 4,4'-dicyanatooctafluorobiphenyl, 2,4'- or 4,4'-dicyanatodiphenylmethane, bis(4-cyanato-3,5-dimethylphenyl)methane, 1,1-bis(4-cyanatophenyl)ethane, 1,1-bis(4-cyanatophenyl)propane, 2,2-bis(4-cyanatophenyl)propane, 2,2-bis(3-allyl-4-cyanatophenyl)propane, 2,2-bis(4-cyanato-3-methylphenyl)propane, 2,2-bis(2-cyanato-5-biphenylyl)propane propane, 2,2-bis(4-cyanatophenyl)hexafluoropropane, 2,2-bis(4-cyanato-3,5-dimethylphenyl)propane, 1,1-bis(4-cyanatophenyl)butane, 1,1-bis(4-cyanatophenyl)isobutane, 1,1-bis(4-cyanatophenyl)pentane, 1,1-bis(4-cyanatophenyl)-3-methylbutane, 1,1-bis(4-cyanatophenyl)-2-methylbutane, 1,1-bis(4-cyanatophenyl)-2,2-dimethylpropane, 2,2-bis(4-cyanatophenyl) Butane, 2,2-bis(4-cyanatophenyl)pentane, 2,2-bis(4-cyanatophenyl)hexane, 2,2-bis(4-cyanatophenyl)-3-methylbutane, 2,2-bis(4-cyanatophenyl)-4-methylpentane, 2,2-bis(4-cyanatophenyl)-3,3-dimethylbutane, 3,3-bis(4-cyanatophenyl)hexane, 3,3-bis(4-cyanatophenyl)heptane, 3,3-bis(4-cyanatophenyl)octane, 3,3-bis(4-cyanatophenyl)-2-methylpentane, 3,3-bis(4-cyanatophenyl)-2-methylpentane, bis(4-cyanatophenyl)-2-methylhexane, 3,3-bis(4-cyanatophenyl)-2,2-dimethylpentane, 4,4-bis(4-cyanatophenyl)-3-methylheptane, 3,3-bis(4-cyanatophenyl)-2-methylheptane, 3,3-bis(4-cyanatophenyl)-2,2-dimethylhexane, 3,3-bis(4-cyanatophenyl)-2,4-dimethylhexane, 3,3-bis(4-cyanatophenyl)-2,2,4-trimethylpentane, 2,2-bis(4-cyanatophenyl)-1,1,1,3,3,3-Hexafluoropropane, bis(4-cyanatophenyl)phenylmethane, 1,1-bis(4-cyanatophenyl)-1-phenylethane, bis(4-cyanatophenyl)biphenylmethane, 1,1-bis(4-cyanatophenyl)cyclopentane, 1,1-bis(4-cyanatophenyl)cyclohexane, 2,2-bis(4-cyanato-3-isopropylphenyl)propane, 1,1-bis(3-cyclohexyl-4-cyanatophenyl)cyclohexane, bis(4-cyanatophenyl)diphenylmethane, bis(4-cyanatophenyl)-2,2 -Dichloroethylene, 1,3-bis[2-(4-cyanatophenyl)-2-propyl]benzene, 1,4-bis[2-(4-cyanatophenyl)-2-propyl]benzene, 1,1-bis(4-cyanatophenyl)-3,3,5-trimethylcyclohexane, 4-[bis(4-cyanatophenyl)methyl]biphenyl, 4,4-dicyanatobenzophenone, 1,3-bis(4-cyanatophenyl)-2-propen-1-one, bis(4-cyanatophenyl)ether, bis(4-cyanatophenyl)sulfide, bis(4-cyanatophenyl)sulfone, 4-Cyanatobenzoic acid-4-cyanatophenyl ester (4-cyanatophenyl-4-cyanatobenzoate), bis-(4-cyanatophenyl)carbonate, 1,3-bis(4-cyanatophenyl)adamantane, 1,3-bis(4-cyanatophenyl)-5,7-dimethyladamantane, 3,3-bis(4-cyanatophenyl)isobenzofuran-1(3H)-one (cyanate of phenolphthalein), 3,3-bis(4-cyanato-3-methylphenyl)isobenzofuran-1(3H)-one (cyanate of o-cresolphthalein), 9 ,9-Bis(4-cyanatophenyl)fluorene, 9,9-bis(4-cyanato-3-methylphenyl)fluorene, 9,9-bis(2-cyanato-5-biphenylyl)fluorene, tris(4-cyanatophenyl)methane, 1,1,1-tris(4-cyanatophenyl)ethane, 1,1,3-tris(4-cyanatophenyl)propane, α,α,α'-tris(4-cyanatophenyl)-1-ethyl-4-isopropylbenzene, 1,1,2,2-tetrakis(4-cyanatophenyl)ethane, tetrakis(4-cyanatophenyl)methane, 2,4,6-Tris(N-methyl-4-cyanatoanilino)-1,3,5-triazine, 2,4-bis(N-methyl-4-cyanatoanilino)-6-(N-methylanilino)-1,3,5-triazine, bis(N-4-cyanato-2-methylphenyl)-4,4'-oxydiphthalimide, bis(N-3-cyanato-4-methylphenyl)-4,4'-oxydiphthalimide, bis(N-4-cyanatophenyl)-4,4'-oxydiphthalimide, bis(N-4-cyanato-2-methylphenyl)-4,4'-(hexafluoroisopropylidene)diphthalimide, tris(3,5-dimethyl-4-cyanatobenzyl)isocyanurate, 2-phenyl-3,3-bis(4-cyanatophenyl)phthalimidine, 2-(4-methylphenyl) 1-methyl-3,3-bis(4-cyanatophenyl)indolin-2-one, 2-phenyl-3,3-bis(4-cyanatophenyl)indolin-2-one, phenol novolac resin and cresol novolac resin (residual resins obtained by reacting phenol, alkyl-substituted phenol or halogen-substituted phenol with formaldehyde compounds such as formalin or paraformaldehyde in an acidic solution by a known method), trisphenol novolac resin (residual resins obtained by reacting hydroxybenzaldehyde with phenol in the presence of an acidic catalyst), fluorene novolac resin (residual resins obtained by reacting fluorenone compounds with 9,9-bis(hydroxyaryl)fluorenes in the presence of an acid catalyst), phenol aralkyl resins, cresol aralkyl resins, naphthol aralkyl resins and biphenyl aralkyl resins (residues obtained by reacting a bishalogenomethyl compound such as Ar5-(CH2Z')2 with a phenol compound with or without an acid catalyst by a known method, a bis(alkoxymethyl) compound such as Ar5-(CH2OR)2 or a bis(hydroxymethyl) compound such as Ar5-(CH2OH)2 with a phenol compound in the presence of an acid catalyst, or a polycondensation of an aromatic aldehyde compound, an aralkyl compound or a phenol compound), phenol-modified Examples of the cyanate ester include xylene formaldehyde resin (a known method in which a xylene formaldehyde resin is reacted with a phenolic compound in the presence of an acid catalyst), modified naphthalene formaldehyde resin (a known method in which a naphthalene formaldehyde resin is reacted with a hydroxy-substituted aromatic compound in the presence of an acid catalyst), phenol-modified dicyclopentadiene resin, and phenolic resin having a polynaphthylene ether structure (a known method in which a polyhydroxynaphthalene compound having two or more phenolic hydroxy groups in one molecule is dehydrated and condensed in the presence of a basic catalyst), which are cyanate esterified in the same manner as described above, but are not particularly limited. These cyanate ester compounds may be used alone or in combination of two or more.

[0056] Among these, phenol novolac type cyanate ester compounds, naphthol aralkyl type cyanate ester compounds, naphthylene ether type cyanate ester compounds, bisphenol A type cyanate ester compounds, bisphenol M type cyanate ester compounds, and diallyl bisphenol type cyanate ester compounds are preferred, and naphthol aralkyl type cyanate ester compounds are particularly preferred.

[0057] The cured products of the resin compositions using these cyanate ester compounds have excellent properties such as heat resistance and copper foil adhesion.

[0058] The content of the cyanate ester compound (F) in the resin composition according to the present embodiment can be appropriately set according to the desired properties, and is not particularly limited. Specifically, the content of the cyanate ester compound (F) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and may be 3 parts by mass or more, 5 parts by mass or more, when the resin solid content in the resin composition is 100 parts by mass. In addition, the upper limit of the content is preferably 90 parts by mass or less, more preferably 80 parts by mass or less, more preferably less than 70 parts by mass, even more preferably 60 parts by mass or less, and may be 50 parts by mass or less, 40 parts by mass or less. By setting it in such a range, it is possible to give better low dielectric constant and low dielectric loss tangent. The cyanate ester compound (F) may be used alone or in combination of two or more. When two or more types are used, the total amount is preferably within the above range.

[0059] [Other ingredients] Furthermore, the resin composition according to the present embodiment may contain, within a range in which the desired properties are obtained, polyphenylene ether compounds other than the polyphenylene ether compound (B), epoxy compounds, phenol compounds, oxetane resins, benzoxazine compounds, thermoplastic elastomers not listed in the block copolymer (C) having a styrene skeleton (hereinafter referred to as "other thermoplastic elastomers"), fillers (G), curing accelerators, organic solvents, etc. By using these in combination, desired properties such as low dielectric constant, low dielectric loss tangent, flame resistance, and low thermal expansion can be improved.

[0060] In the resin composition according to the present embodiment, the total amount of the polyphenylene ether compound other than the polyphenylene ether compound (B) and the other thermoplastic elastomer is preferably 3% by mass or less, more preferably 1% by mass or less, of the resin solid content. By adopting such a constitution, the effect of the present invention is more effectively exhibited.

[0061] [Epoxy compounds] The epoxy compound is not particularly limited as long as it is a compound or resin having one or more (preferably 2 to 12, more preferably 2 to 6, even more preferably 2 to 4, still more preferably 2 or 3, and even more preferably 2) epoxy groups in one molecule, and a wide range of compounds commonly used in the field of printed wiring boards can be used. Examples of epoxy compounds include bisphenol A type epoxy resins, bisphenol E type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, phenol novolac type epoxy resins, bisphenol A novolac type epoxy resins, glycidyl ester type epoxy resins, aralkyl novolac type epoxy resins, biphenyl aralkyl type epoxy resins, naphthylene ether type epoxy resins, cresol novolac type epoxy resins, multifunctional phenol type epoxy resins, naphthalene type epoxy resins, anthracene type epoxy resins, naphthalene skeleton modified novolac type epoxy resins, phenol aralkyl type epoxy resins, naphthol aralkyl type epoxy resins, dicyclopentadiene type epoxy resins, biphenyl type epoxy resins, alicyclic epoxy resins, polyol type epoxy resins, phosphorus-containing epoxy resins, glycidyl amines, glycidyl esters, compounds in which the double bonds of butadiene are epoxidized, compounds obtained by reacting hydroxyl group-containing silicone resins with epichlorohydrin, etc. These epoxy resins may be used alone or in combination of two or more. Among these, from the viewpoint of further improving flame retardancy and heat resistance, biphenyl aralkyl type epoxy resins, naphthylene ether type epoxy resins, polyfunctional phenol type epoxy resins, and naphthalene type epoxy resins are preferred.

[0062] [Phenol compounds] The phenol compound is not particularly limited as long as it is a compound or resin having one or more (preferably 2 to 12, more preferably 2 to 6, even more preferably 2 to 4, still more preferably 2 or 3, and even more preferably 2) phenolic hydroxy groups in one molecule. Examples of the phenol compound include bisphenol A type phenolic resin, bisphenol E type phenolic resin, bisphenol F type phenolic resin, bisphenol S type phenolic resin, phenol novolac resin, bisphenol A novolac type phenolic resin, glycidyl ester type phenolic resin, aralkyl novolac phenolic resin, biphenyl aralkyl type phenolic resin, cresol novolac type phenolic resin, polyfunctional phenolic resin, naphthol resin, naphthol novolac resin, polyfunctional naphthol resin, anthracene type phenolic resin, naphthalene skeleton modified novolac type phenolic resin, phenol aralkyl type phenolic resin, naphthol aralkyl type phenolic resin, dicyclopentadiene type phenolic resin, biphenyl type phenolic resin, alicyclic phenolic resin, polyol type phenolic resin, and phosphorus-containing phenolic resins. These phenolic resins may be used alone or in combination of two or more kinds. Among these, from the viewpoint of further improving flame resistance, at least one selected from the group consisting of biphenyl aralkyl type phenolic resins, naphthol aralkyl type phenolic resins, phosphorus-containing phenolic resins, and hydroxyl group-containing silicone resins is preferred.

[0063] [Oxetane resin] The oxetane resin is not particularly limited, and examples thereof include oxetane, alkyl oxetane (e.g., 2-methyl oxetane, 2,2-dimethyl oxetane, 3-methyl oxetane, 3,3-dimethyl oxetane, etc.), 3-methyl-3-methoxymethyl oxetane, 3,3-di(trifluoromethyl)perfluoro, 2-chloromethyl oxetane, 3,3-bis(chloromethyl)oxetane, biphenyl type oxetane, OXT-101 (product of Toagosei Co., Ltd.), OXT-121 (product of Toagosei Co., Ltd.), etc. These oxetane resins may be used alone or in combination of two or more kinds.

[0064] [Benzoxazine compounds] The benzoxazine compound is not particularly limited as long as it is a compound having two or more dihydrobenzoxazine rings in one molecule, and examples thereof include bisphenol A-type benzoxazine BA-BXZ (product of Konishi Chemical Co., Ltd.), bisphenol F-type benzoxazine BF-BXZ (product of Konishi Chemical Co., Ltd.), bisphenol S-type benzoxazine BS-BXZ (product of Konishi Chemical Co., Ltd.), etc. These benzoxazine compounds may be used alone or in combination of two or more kinds.

[0065] [Other thermoplastic elastomers] The "other thermoplastic elastomer" is distinguished from the "block copolymer (C) having a styrene skeleton". The "block copolymer (C) having a styrene skeleton" refers to an elastomer having a polystyrene block structure and being a block copolymer, and the "other thermoplastic elastomer" refers to other elastomers. That is, random copolymers, block copolymers not having a styrene skeleton, etc. are included. Examples of the other thermoplastic elastomers include at least one selected from the group consisting of polyisoprene, polybutadiene, styrene-butadiene random copolymers, butyl rubber, ethylene-propylene rubber, fluororubber, silicone rubber, hydrogenated compounds thereof, and alkyl compounds thereof. Among these, from the viewpoint of superior compatibility with the polyphenylene ether compound (B), at least one selected from the group consisting of polyisoprene, polybutadiene, styrene-butadiene random copolymers, butyl rubber, and ethylene-propylene rubber is more preferable.

[0066] [Filler (G)] As the filler (G), a known one can be appropriately used, and the type is not particularly limited, and one generally used in the art can be suitably used. Specifically, silicas such as natural silica, fused silica, synthetic silica, amorphous silica, aerosil, and hollow silica, white carbon, titanium white, zinc oxide, magnesium oxide, zirconium oxide, boron nitride, aggregated boron nitride, silicon nitride, aluminum nitride, barium sulfate, aluminum hydroxide, aluminum hydroxide heat-treated product (aluminum hydroxide heat-treated to remove part of the water of crystallization), boehmite, metal hydrates such as magnesium hydroxide, molybdenum compounds such as molybdenum oxide and zinc molybdate, zinc borate, zinc stannate, alumina, clay, etc. Examples of fillers include inorganic fillers such as cellulose, kaolin, talc, calcined clay, calcined kaolin, calcined talc, mica, E-glass, A-glass, NE-glass, C-glass, L-glass, D-glass, S-glass, M-glass G20, glass short fibers (including glass fine powders such as E-glass, T-glass, D-glass, S-glass, and Q-glass), hollow glass, and spherical glass, as well as organic fillers such as styrene-type, butadiene-type, and acrylic-type rubber powders, core-shell-type rubber powders, silicone resin powders, silicone rubber powders, and silicone composite powders. These fillers may be used alone or in combination of two or more.

[0067] Among these, one or more selected from the group consisting of silica, aluminum hydroxide, boehmite, magnesium oxide and magnesium hydroxide are suitable. By using these fillers (G), the properties such as thermal expansion properties, dimensional stability, and flame retardancy of the resin composition are improved.

[0068] The content of the filler (G) in the resin composition can be appropriately set according to the desired properties, and is not particularly limited. When the filler (G) is contained, the content is preferably 50 parts by mass or more when the resin solid content in the resin composition is 100 parts by mass. In addition, the upper limit of the content of the filler (G) is preferably 1600 parts by mass or less, more preferably 500 parts by mass or less, and particularly preferably 300 parts by mass or less when the resin solid content in the resin composition is 100 parts by mass. Alternatively, the filler (G) may be 75 parts by mass to 250 parts by mass, or 100 parts by mass to 200 parts by mass. By setting the content of the filler (G) within this range, the moldability of the resin composition becomes good. The resin composition may contain only one type of filler (G), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0069] Here, when using the filler (G), it is preferable to use at least one selected from the group consisting of a silane coupling agent and a wetting and dispersing agent in combination. As the silane coupling agent, those generally used for surface treatment of inorganic substances can be suitably used, and the type is not particularly limited. Specifically, aminosilanes such as γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxylane, epoxysilanes such as γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, vinylsilanes such as γ-methacryloxypropyltrimethoxysilane and vinyl-tri(β-methoxyethoxy)silane, cationic silanes such as N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride, phenylsilanes, etc. The silane coupling agents may be used alone or in combination of two or more. In addition, those generally used for paints can be suitably used, and the type is not particularly limited. Preferably, a copolymer-based wetting and dispersing agent is used, and specific examples thereof include Disperbyk-110, 111, 161, 180, 2009, 2152, BYK-W996, BYK-W9010, BYK-W903, and BYK-W940 manufactured by BYK Japan Co., Ltd. The wetting and dispersing agent may be used alone or in combination of two or more kinds. The content of the silane coupling agent is not particularly limited, and may be about 1 to 5 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition. The content of the dispersant (particularly the wetting dispersant) is not particularly limited, and may be, for example, about 0.5 to 5 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition.

[0070] [Cure accelerator] The resin composition according to the present embodiment may contain a curing accelerator for appropriately adjusting the curing speed. Examples of the curing accelerator include those commonly used as curing accelerators, such as maleimide compounds, cyanate ester compounds, and epoxy compounds, and include organometallic salts (e.g., zinc octylate, zinc naphthenate, cobalt naphthenate, copper naphthenate, iron acetylacetonate, nickel octylate, manganese octylate, etc.), phenolic compounds (e.g., phenol, xylenol, cresol, resorcin, catechol, octylphenol, nonylphenol, etc.), alcohols (e.g., 1-butanol, 2-ethylhexanol, etc.), imidazoles (e.g., 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenyl-4,5 -dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, etc.), and derivatives of these imidazoles such as adducts of carboxylic acids or their acid anhydrides, amines (e.g., dicyandiamide, benzyldimethylamine, 4-methyl-N,N-dimethylbenzylamine, etc.), phosphorus compounds (e.g., phosphine compounds, phosphine oxide compounds, phosphonium salt compounds, diphosphine compounds, etc.), epoxy-imidazole adduct compounds, peroxides (e.g., benzoyl peroxide, p-chlorobenzoyl peroxide, di-t-butyl peroxide, diisopropyl peroxycarbonate, di-2-ethylhexyl peroxycarbonate, etc.), azo compounds (e.g., azobisisobutyronitrile, etc.). The curing accelerator may be used alone or in combination of two or more. The content of the curing accelerator may usually be about 0.005 parts by mass to 10 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition.

[0071] The resin composition according to the present embodiment may contain various polymer compounds such as thermosetting resins, thermoplastic resins, and oligomers thereof, and various additives other than the above components. Examples of additives include ultraviolet absorbers, antioxidants, photopolymerization initiators, fluorescent brighteners, photosensitizers, dyes, pigments, thickeners, flow control agents, lubricants, defoamers, dispersants, leveling agents, gloss agents, and polymerization inhibitors. These additives may be used alone or in combination of two or more.

[0072] [Organic solvents] The resin composition according to the present embodiment may contain an organic solvent. In this case, the resin composition according to the present embodiment is in a form (solution or varnish) in which at least a part, preferably all, of the various resin components described above are dissolved or compatible in the organic solvent. The organic solvent is not particularly limited as long as it is a polar organic solvent or a non-polar organic solvent that can dissolve or compatible at least a part, preferably all, of the various resin components described above. Examples of the polar organic solvent include ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), cellosolves (e.g., propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, etc.), esters (e.g., ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, isoamyl acetate, ethyl lactate, methyl methoxypropionate, methyl hydroxyisobutyrate, etc.), amides (e.g., dimethoxyacetamide, dimethylformamides, etc.), and examples of the non-polar organic solvent include aromatic hydrocarbons (e.g., toluene, xylene, etc.). These organic solvents may be used alone or in combination of two or more.

[0073] [Preparation of resin composition] The resin composition according to the present embodiment can be prepared according to a conventional method, and the preparation method is not particularly limited as long as it is a method that can obtain a resin composition that uniformly contains the maleimide compound (A) having an aromatic ring in the main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, the polyphenylene ether compound (B) represented by general formula (1) having a number average molecular weight of 1000 to 7000, the block copolymer (C) having a styrene skeleton, and the other optional components described above. For example, the resin composition according to the present embodiment can be easily prepared by sequentially blending the maleimide compound (A), the polyphenylene ether compound (B) represented by general formula (1), and the block copolymer (C) having a styrene skeleton in a solvent and thoroughly stirring the mixture. In the resin composition according to the present embodiment, the sum of the masses of the maleimide compound (A), the polyphenylene ether compound (B) represented by general formula (1), and the block copolymer (C) having a styrene skeleton preferably accounts for 40% by mass or more of the resin solid content contained in the resin composition, more preferably accounts for 45% by mass or more, and may even account for 50% by mass or more.

[0074] [Application] The resin composition according to this embodiment can be suitably used as a resin sheet, a prepreg, an insulating layer for a printed wiring board, a laminate, or a material for a semiconductor package.

[0075] [Resin sheet] The resin sheet according to the present embodiment has a support and a layer formed from the resin composition according to the present embodiment arranged on the surface of the support. The resin sheet can be used as a build-up film or a dry film solder resist. The method for producing the resin sheet is not particularly limited, but for example, a method of obtaining a resin sheet by applying (coating) a solution in which the resin composition according to the present embodiment is dissolved in a solvent to a support and drying the solution can be mentioned.

[0076] Examples of the support used here include, but are not limited to, polyethylene film, polypropylene film, polycarbonate film, polyethylene terephthalate film, ethylene tetrafluoroethylene copolymer film, and release films obtained by applying a release agent to the surface of these films, organic film substrates such as polyimide film, conductor foils such as copper foil and aluminum foil, glass plate, SUS plate, FRP, and other plate-shaped supports. As for the copper foil, the ten-point average roughness Rz of the surface of the copper foil on the side on which the layer on which the resin composition according to the present embodiment is formed is preferably 0.3 μm or more and 10 μm or less. This is because the plating adhesion can be improved by making it 0.3 μm or more. In addition, if it is larger than 10 μm, the thickness of the layer on which the resin composition according to the present embodiment is formed must be increased in order to ensure insulation. A more preferable range of the ten-point average roughness Rz of the surface of the copper foil is, for example, 0.6 μm or more and 2.5 μm or less. It is preferable that the ten-point average roughness Rz of the surface of the copper foil is smaller than the thickness of the layer on which the resin composition according to the present embodiment is formed. This is to enhance insulation. The ten-point average roughness Rz of the surface of the copper foil can be measured using a commercially available shape measuring microscope (laser microscope, for example, "VK-X1000" (product name) manufactured by Keyence Corporation).

[0077] The thickness of the copper foil is not particularly limited, but in consideration of the surface roughening treatment, a range of 1 μm to 18 μm is preferable, and a range of 2 μm to 15 μm is more preferable because it allows the suitable production of thin printed wiring boards and semiconductor element mounting boards.

[0078] Examples of the application method (coating method) include a method in which a solution in which the resin composition according to this embodiment is dissolved in a solvent is applied onto a support using a gravure coater, a bar coater, a die coater, a doctor blade, a baker applicator, or the like.

[0079] In the preparation of the resin sheet according to the present embodiment, the drying conditions for removing the solvent are not particularly limited, but from the viewpoint of facilitating removal of the solvent in the resin composition and suppressing the progress of curing during drying, a temperature of 20°C to 200°C for 1 minute to 90 minutes is preferred. In addition, in the resin sheet according to the present embodiment, the resin composition can be used in an uncured state in which the solvent has only been dried, or can be used in a semi-cured (B-stage) state as necessary. Furthermore, the thickness of the resin layer of the resin sheet according to the present embodiment can be adjusted by the concentration and coating thickness of the solution of the resin composition according to the present embodiment, and is not particularly limited, but from the viewpoint of facilitating removal of the solvent during drying, a thickness of 0.1 μm to 500 μm is preferred.

[0080] [Prepreg] The prepreg according to the present embodiment is formed from a substrate and the resin composition according to the present embodiment. The prepreg according to the present embodiment can be obtained, for example, by impregnating or applying the resin composition according to the present embodiment to a substrate, and then semi-curing the substrate by drying at 120°C to 220°C for about 2 to 15 minutes. In this case, the amount of the resin composition attached to the substrate, that is, the amount of the resin composition (including the filler (G)) relative to the total amount of the semi-cured prepreg, is preferably in the range of 20% by mass to 90% by mass.

[0081] The substrate is not particularly limited as long as it is a substrate used in various printed wiring board materials. Examples of the material of the substrate include glass fibers (e.g., E glass, D glass, L glass, S glass, T glass, Q glass, UN glass, NE glass, spherical glass), inorganic fibers other than glass (e.g., quartz), and organic fibers (e.g., polyimide, polyamide, polyester, liquid crystal polyester, polytetrafluoroethylene). The form of the substrate is not particularly limited, and examples thereof include woven fabric, nonwoven fabric, roving, chopped strand mat, surfacing mat, and the like. These substrates may be used alone or in combination of two or more. Among these substrates, from the viewpoint of dimensional stability, woven fabrics that have been subjected to ultra-opening treatment and clogging treatment are preferred, and from the viewpoint of moisture absorption and heat resistance, glass woven fabrics that have been surface-treated with silane coupling agents such as epoxy silane treatment and amino silane treatment are preferred.

[0082] This prepreg can be obtained, for example, by impregnating or coating a substrate with the resin composition, and then semi-curing (B-stage) the substrate by drying at 120°C to 220°C for about 2 to 15 minutes. In this case, the amount of the resin composition (including the cured product of the resin composition) attached to the substrate, that is, the amount of the resin composition (including the filler (G)) relative to the total amount of the semi-cured prepreg, is preferably in the range of 20% by mass to 99% by mass. The thickness and mass of the substrate are not particularly limited, but a substrate having a thickness of about 0.01 mm to 0.3 mm is usually preferably used. In particular, from the viewpoints of strength and water absorption, the substrate should have a thickness of 200 μm or less and a mass of 250 g / m 2 The following woven fabrics are preferred:

[0083] [Laminate] A laminate is formed by heating and pressurizing a laminate containing one or more prepregs to harden the prepregs. The molding method and molding conditions for the laminate are not particularly limited, and general techniques and conditions can be used. For example, a multi-stage press machine, a multi-stage vacuum press machine, a continuous molding machine, an autoclave molding machine, etc. can be used during molding. In molding (lamination molding), the temperature is 100°C to 300°C, and the pressure is a surface pressure of 2 kgf / cm. 2~100kgf / cm 2 The heating time is generally in the range of 0.05 to 5 hours. Furthermore, if necessary, post-curing can be performed at a temperature of 150°C to 300°C. In particular, when a multi-stage press is used, from the viewpoint of sufficiently promoting the curing of the prepreg, a temperature of 200°C to 250°C and a pressure of 10 kgf / cm are preferable. 2 ~40kgf / cm 2 The heating time is preferably 80 to 130 minutes, the temperature is 215 to 235°C, and the pressure is 25 kgf / cm 2 ~35kgf / cm 2 The heating time is more preferably 90 to 120 minutes.

[0084] [Printed wiring board] The printed wiring board according to the present embodiment includes an insulating layer and a conductor layer disposed on the surface of the insulating layer, and the insulating layer includes a layer formed from the resin composition according to the present embodiment. The resin sheet according to the present embodiment can be used for a printed wiring board. Here, the printed wiring board can be obtained by using the resin sheet according to the present embodiment, for example, a copper foil with an insulating resin layer (resin composition layer) as a build-up material for a metal foil-clad laminate in which an insulating resin layer called a core substrate is completely cured.

[0085] A conductor circuit is formed on the surface of the metal foil-clad laminate by the metal foil of a commonly used metal foil-clad laminate and / or a conductor layer obtained by plating after peeling off the metal foil, etc. The substrate of the metal foil-clad laminate is not particularly limited, but is mainly a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate.

[0086] In this embodiment, build-up refers to laminating the resin sheet of this embodiment, for example the insulating resin layer of a copper foil with an insulating resin layer, onto the metal foil and / or conductor layer on the surface of a metal foil-clad laminate.

[0087] Usually, when an insulating resin layer (resin composition layer) is laminated on a metal foil-clad laminate using an adhesive film or the like as a build-up material, the resulting printed wiring board has an insulating resin layer on one or both sides. A conductor layer is to be formed on this insulating resin layer, but since the insulating resin layer has a low surface roughness after curing, roughening treatment including desmearing is usually performed to form irregularities, and then the conductor layer is formed using electroless plating and / or electrolytic plating.

[0088] When the resin sheet of this embodiment, for example, copper foil with an insulating resin layer, is laminated on a metal foil-clad laminate as a build-up material, the resulting printed wiring board has copper foil on one or both sides. Therefore, a circuit pattern can be formed directly on the copper foil without plating, so that high-density fine wiring can be formed. In addition, when manufacturing a printed wiring board or a substrate for mounting semiconductor elements, even if plating is performed after etching the copper foil, the surface shape of the copper foil surface is transferred to the insulating resin layer, so that the adhesion between the insulating resin layer and the plating is improved.

[0089] In the manufacture of printed wiring boards, holes such as via holes and / or through holes are formed as necessary to electrically connect each conductor layer. The holes are usually formed using a mechanical drill, a carbon dioxide laser, a UV laser, a YAG laser, etc. After the holes are formed, a roughening treatment including a desmear treatment is performed.

[0090] Generally, the roughening treatment comprises a swelling step, a surface roughening and smear dissolving step, and a neutralization step.

[0091] The swelling step is performed by swelling the surface of the insulating resin layer using a swelling agent. The swelling agent is not particularly limited as long as it can improve the wettability of the surface of the insulating resin layer and swell the surface of the insulating resin layer to such an extent that oxidative decomposition is promoted in the subsequent surface roughening and smear dissolving steps. Examples of the swelling agent include an alkaline solution, a surfactant solution, and the like.

[0092] The surface roughening and smear dissolving process is carried out using an oxidizing agent. Examples of the oxidizing agent include an alkaline permanganate solution, and preferred examples include an aqueous potassium permanganate solution and an aqueous sodium permanganate solution. Such an oxidizing agent treatment is called wet desmear, but in addition to the wet desmear, other known roughening treatments such as dry desmear by plasma treatment or UV treatment, mechanical polishing by buffing, sandblasting, etc. may be appropriately combined.

[0093] In the neutralization step, the oxidizing agent used in the previous step is neutralized with a reducing agent. The reducing agent may be an amine-based reducing agent, and specific examples of suitable reducing agents include acidic aqueous solutions such as an aqueous solution of hydroxylamine sulfate, an aqueous solution of ethylenediaminetetraacetic acid, and an aqueous solution of nitrilotriacetic acid.

[0094] In this embodiment, after providing the via holes and / or through holes, or after desmearing the inside of the via holes and / or through holes, it is preferable to perform metal plating to electrically connect each conductor layer. In this embodiment, even if metal plating is performed, the copper foil surface is transferred to the insulating resin layer, so that the adhesion between the insulating resin layer and the metal plating is improved.

[0095] The method of metal plating is not particularly limited, and a method of metal plating used in the manufacture of a normal multilayer printed wiring board can be used as appropriate. The method of metal plating and the type of chemical used for plating are not particularly limited, and a method of metal plating and chemical used in the manufacture of a normal multilayer printed wiring board can be used as appropriate. The chemical used for metal plating may be a commercially available product. The metal plating method is not particularly limited, and examples thereof include treatment with a degreasing liquid, treatment with a soft etching liquid, acid washing, treatment with a pre-dip liquid, treatment with a catalyst liquid, treatment with an accelerator liquid, treatment with a chemical copper liquid, acid washing, and treatment of immersion in a copper sulfate liquid and passing an electric current therethrough.

[0096] In addition, when a semi-cured resin sheet, for example, a copper foil with an insulating resin layer, is used for build-up, the semi-cured insulating resin layer is usually subjected to a heat treatment or the like to completely cure it, thereby obtaining a printed wiring board. In this embodiment, another resin sheet, for example, a copper foil with an insulating resin layer, may be further laminated on the obtained printed wiring board.

[0097] The lamination method in the build-up method is not particularly limited, but a vacuum pressure laminator can be suitably used. In this case, the resin sheet of the present embodiment, for example, a copper foil with an insulating resin layer, can be laminated via an elastic body such as rubber. The lamination conditions are not particularly limited as long as they are conditions used in laminating ordinary printed wiring boards, but for example, a temperature of 70°C to 140°C, 1 kgf / cm 2 ~11kgf / cm 2 The lamination process is carried out under a contact pressure in the range of 100° C. and a reduced atmospheric pressure of 20 hPa or less. After the lamination process, the laminated adhesive film may be smoothed by hot pressing with a metal plate. The lamination process and the smoothing process may be carried out continuously by a commercially available vacuum pressure laminator. After the lamination process or after the smoothing process, a heat curing process may be included. By using the heat curing process, the insulating resin layer can be completely cured. The heat curing conditions vary depending on the types of components contained in the resin composition, but are usually a curing temperature of 170° C. to 220° C. and a curing time of 15 minutes to 200 minutes.

[0098] In this embodiment, the method for forming a circuit pattern on the copper foil on one or both sides of the printed wiring board includes a semi-additive method, a full-additive method, a subtractive method, etc. Among them, the semi-additive method is preferred from the viewpoint of forming a fine wiring pattern.

[0099] An example of a method for forming a circuit pattern by the semi-additive method is a method in which electrolytic plating is selectively performed using a plating resist (pattern plating), the plating resist is then peeled off, and the entire surface is appropriately etched to form a wiring pattern. In the formation of a circuit pattern by the semi-additive method, electroless plating and electrolytic plating are performed in combination, and in this case, it is preferable to perform drying after electroless plating and after electrolytic plating, respectively. The drying after electroless plating is not particularly limited, but is preferably performed at 80°C to 180°C for 10 minutes to 120 minutes, for example, and the drying after electrolytic plating is not particularly limited, but is preferably performed at 130°C to 220°C for 10 minutes to 120 minutes, for example. As the plating, copper plating is preferable.

[0100] An example of a method for forming a circuit pattern by a subtractive method is a method for forming a wiring pattern by selectively removing a conductor layer using an etching resist. Specifically, for example, the method can be performed as follows. A dry film resist (RD-1225 (product name) manufactured by Hitachi Chemical) is laminated (laminated) on the entire surface of the copper foil at a temperature of 110±10°C and a pressure of 0.50±0.02 MPa. Next, exposure is performed along the circuit pattern, and masking is performed. Thereafter, the dry film resist is developed with a 1% aqueous sodium carbonate solution, and finally, the dry film resist is peeled off with an amine-based resist peeling solution. This allows a circuit pattern to be formed on the copper foil.

[0101] In this embodiment, an insulating resin layer and / or a conductor layer may be further laminated on the printed wiring board to obtain a multilayer printed wiring board. The inner layer of the multilayer printed wiring board may have a circuit board. The resin sheet of this embodiment, for example, a copper foil with an insulating resin layer, constitutes one of the insulating resin layers and the conductor layers of the multilayer printed wiring board.

[0102] The lamination method is not particularly limited, and a method generally used in lamination molding of normal printed wiring boards can be used. Examples of lamination methods include a multi-stage press, a multi-stage vacuum press, a laminator, a vacuum laminator, an autoclave molding machine, etc. The temperature during lamination is not particularly limited, but for example, 100°C to 300°C, and the pressure is not particularly limited, but for example, 0.1 kgf / cm 2 ~100kgf / cm 2 (about 9.8 kPa to about 9.8 MPa), the heating time is not particularly limited, but is appropriately selected within the range of, for example, 30 seconds to 5 hours. If necessary, post-curing may be performed within the temperature range of, for example, 150° C. to 300° C. to adjust the degree of cure.

[0103] The above-mentioned prepreg can also be used as the insulating layer of the printed wiring board according to this embodiment. As a method for laminating the prepreg of this embodiment as a build-up material, for example, there is a method in which a required number of prepregs of this embodiment are laminated on the metal foil and / or conductor layer on the surface of a metal foil-clad laminate, and copper foil is further laminated on the outside thereof, and the laminate is heated and pressed to be integrally molded.

[0104] Thus, according to the resin composition, resin sheet, and printed wiring board of the present embodiment, since it contains a maleimide compound (A) having an aromatic ring in the main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) having a number average molecular weight of 1000 to 7000 represented by general formula (1), and a block copolymer (C) having a styrene skeleton, it is possible to obtain excellent low dielectric constant, low dielectric loss tangent, and flexibility, and it is possible to make the film thin and reduce high-frequency signal loss. In addition, since the resin composition of the present embodiment is contained in a prepreg, it is possible to obtain excellent moldability, low dielectric constant, low dielectric loss tangent, and peel strength.

[0105] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to these examples in any way. EXAMPLES

[0106] Example 1 A maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring in the main skeleton, which shows a relative dielectric constant of less than 2.7 at 10 GHz when cured alone and represented by the general formula (6), 40 parts by mass, a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is represented by the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1.

[0107] The obtained varnish was applied to one side of a 12 μm thick copper foil (3EC-M2S-VLP, manufactured by Mitsui Mining & Smelting Co., Ltd.) using a bar coater to obtain a copper-attached resin sheet. The obtained copper-attached resin sheet was heated and dried at 130° C. for 5 minutes using a dryer (pressure-resistant explosion-proof steam dryer, manufactured by Takasugi Seisakusho Co., Ltd.) to obtain a semi-cured copper-attached resin sheet with a resin thickness of 30 μm. Two semi-cured copper-attached resin sheets were heated and laminated so that the resin surfaces of the semi-cured copper-attached resin sheets were in contact with each other, and then the copper foil was peeled off. The two semi-cured copper-attached resin sheets were heated and laminated so that the resin surfaces were in contact with each other, and the copper foil was peeled off. This process was repeated four times to obtain a semi-cured resin sheet with a resin layer thickness of 0.3 mm. This semi-cured resin sheet with a resin layer thickness of 0.3 mm was heated and laminated at a pressure of 25 kg / cm 2 The cured resin was then subjected to vacuum pressing at a temperature of 210°C for 150 minutes to obtain a cured resin plate with a resin layer thickness of 0.3 mm. The cured resin plate was used to evaluate the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility. The results are shown in Table 2.

[0108] The measurement of the dielectric constant of the maleimide compound (A) was carried out by diluting the maleimide compound (A) with methyl ethyl ketone to a solid content of 30 mass%, and applying the maleimide compound (A) diluted with methyl ethyl ketone to one side of a 12 μm thick copper foil (3EC-M2S-VLP, manufactured by Mitsui Mining & Smelting Co., Ltd.) in the same manner as in the manufacturing method of the copper-attached resin sheet shown in Example 1, and drying the obtained copper-attached resin sheet by heating at 130 ° C. for 5 minutes to obtain a semi-cured copper-attached resin sheet with a resin thickness of 30 μm. Two semi-cured copper-attached resin sheets were heated and laminated so that the resin surfaces of the semi-cured copper-attached resin sheets were in contact with each other, and then the copper foil was peeled off. The two semi-cured copper-attached resin sheets were heated and laminated so that the resin surfaces were in contact with each other, and the copper foil was peeled off. This was repeated four times to obtain a semi-cured resin sheet with a resin layer thickness of 0.3 mm. This semi-cured resin sheet with a resin layer thickness of 0.3 mm was pressed under a pressure of 25 kg / cm 2 The laminate was subjected to vacuum pressing at a temperature of 210° C. for 150 minutes to prepare a cured resin plate having a resin layer thickness of 0.3 mm. The dielectric constant of the cured resin plate was measured.

[0109] Example 2 25 parts by mass of a maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring in the main skeleton, exhibiting a relative dielectric constant at 10 GHz of less than 2.7 when cured alone and represented by general formula (6), and a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Co., Ltd.) in which, in general formula (10), X is represented by general formula (11) and -(Y-O)n2- is a polymerized structural unit of general formula (14). 35 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), 25 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), and 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0110] Example 3 15 parts by mass of a maleimide compound (A) (MIR-5000, which has a dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring in the main skeleton, which has a dielectric constant of less than 2.7 at 10 GHz when cured alone and is represented by general formula (6), and a polyphenylene ether compound (B) (OPE-2 St2200, manufactured by Mitsubishi Gas Chemical Co., Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) 15 parts by mass, styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) 25 parts by mass, 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as phosphorus-based flame retardant (E), 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R506 ,R 507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512 A biphenyl-type maleimide compound (D) (MIR-3000, dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which n is a hydrogen atom and the average value of n5 is 1.4 was mixed in an amount of 30 parts by mass, and the solid content was diluted to 60% by mass with methyl ethyl ketone to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was produced in the same manner as in Example 1, and the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0111] Example 4 A maleimide compound (A) (X9-450, manufactured by DIC Corporation) having an aromatic ring in the main skeleton, which has a dielectric constant of less than 2.7 at 10 GHz when cured alone and is represented by the general formula (27), and having a dielectric constant of 2.4 when cured alone, were mixed with 40 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Company, Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is represented by the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), and the solid content was diluted to 60% by mass with methyl ethyl ketone to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin-cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin-cured plate are shown in Table 2.

[0112] Example 5 25 parts by mass of a maleimide compound (A) (X9-450, manufactured by DIC Corporation) having an aromatic ring in the main skeleton, which has a dielectric constant of less than 2.7 at 10 GHz when cured alone and is represented by general formula (27), and a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.) in which, in general formula (10), X is general formula (11) and -(Y-O)n2- is a polymerized structural unit of general formula (14). 35 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), 25 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), and 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0113] Example 6 15 parts by mass of a maleimide compound (A) (X9-450, which has a dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) having an aromatic ring in the main skeleton, which has a dielectric constant of less than 2.7 at 10 GHz when cured alone and is represented by general formula (27); 15 parts by mass of a polyphenylene ether compound (B) (OPE-2S 15 parts by mass of styrene-butadiene block copolymer (C) (TR2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), 25 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as phosphorus-based flame retardant (E), 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R506 ,R 507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512 A biphenyl-type maleimide compound (D) (MIR-3000, dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which n is a hydrogen atom and the average value of n5 is 1.4 was mixed in an amount of 30 parts by mass, and the solid content was diluted to 60% by mass with methyl ethyl ketone to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was produced in the same manner as in Example 1, and the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0114] Example 7 15 parts by mass of a maleimide compound (A) (X9-450, which has a dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) having an aromatic ring in the main skeleton, which has a dielectric constant of less than 2.7 at 10 GHz when cured alone and is represented by general formula (27); 15 parts by mass of a polyphenylene ether compound (B) (OPE-2S 15 parts by mass of styrene-butadiene block copolymer (C) (TR2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), 25 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as phosphorus-based flame retardant (E), 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R 506 ,R 507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512A biphenyl-type maleimide compound (D) (MIR-3000, the relative dielectric constant when cured alone is 2.7, manufactured by Nippon Kayaku Co., Ltd.) having an average value of n5 of 1.4 and 29 parts by mass of the cyanate ester compound (SNCN) (F) obtained in Synthesis Example 1 below was mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0115] (Synthesis Example 1) Synthesis of cyanate ester compound 300 g (1.28 mol in terms of OH groups) of 1-naphthol aralkyl resin (manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.) and 194.6 g (1.92 mol) of triethylamine (1.5 mol per 1 mol of hydroxyl groups) were dissolved in 1800 g of dichloromethane to prepare solution 1. 125.9g (2.05mol) of cyanogen chloride (1.6mol per 1mol of hydroxyl group), 293.8g of dichloromethane, 194.5g (1.92mol) of 36% hydrochloric acid (1.5mol per 1mol of hydroxyl group), and 1205.9g of water were poured in over 30 minutes while stirring and keeping the liquid temperature at -2℃ to -0.5℃. After the end of pouring in solution 1, the mixture was stirred at the same temperature for 30 minutes, and then a solution (solution 2) in which 65g (0.64mol) of triethylamine (0.5mol per 1mol of hydroxyl group) was dissolved in 65g of dichloromethane was poured in over 10 minutes. After the end of pouring in solution 2, the mixture was stirred at the same temperature for 30 minutes to complete the reaction. The reaction solution was then left to stand to separate the organic and aqueous phases. The resulting organic phase was washed five times with 1300 g of water. The electrical conductivity of the wastewater from the fifth wash was 5 μS / cm, confirming that the ionic compounds were sufficiently removed by washing with water. The organic phase after washing with water was concentrated under reduced pressure and finally concentrated to dryness at 90°C for 1 hour to obtain 331 g of the desired naphthol aralkyl type cyanate ester compound (SNCN) (orange viscous material). The mass average molecular weight Mw of the obtained SNCN was 600. In addition, the IR spectrum of SNCN was 2250 cm -1 (cyanate ester group) absorption was observed, and no hydroxyl group absorption was observed.

[0116] Example 8 15 parts by mass of a maleimide compound (A) (X9-470, which has a dielectric constant of 2.4 when cured alone, manufactured by DIC Corporation) having an aromatic ring in the main skeleton, which has a dielectric constant of less than 2.7 at 10 GHz and is represented by general formula (27) when cured alone, and a polyphenylene ether compound (B) (OPE-2S 15 parts by mass of styrene-butadiene block copolymer (C) (TR2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), 25 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as phosphorus-based flame retardant (E), 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R 506 ,R 507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512A biphenyl-type maleimide compound (D) (MIR-3000, the relative dielectric constant when cured alone is 2.7, manufactured by Nippon Kayaku Co., Ltd.) having an average value of n5 of 1.4 and 29 parts by mass of SNCN (F) obtained from Synthesis Example 1 shown in Example 7 were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0117] Example 9 A maleimide compound (A) (X9-470, manufactured by DIC Corporation) having an aromatic ring in the main skeleton, which shows a relative dielectric constant of less than 2.7 at 10 GHz when cured alone and is represented by the general formula (27), and a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Company, Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is represented by the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 3. Thereafter, a resin-cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin-cured plate are shown in Table 2.

[0118] Comparative Example 1 In the general formula (3), R 501 ,R 502 ,R 503 ,R 504 ,R 505 ,R 506 ,R 507 ,R 508 ,R 509 ,R 510 ,R 511 ,R 512A biphenyl-type maleimide compound (D) (MIR-3000, having a relative dielectric constant of 2.7 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) in which n5 is a hydrogen atom and the average value of n5 is 1.4, 40 parts by mass, a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is a general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin-cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin-cured plate are shown in Table 2.

[0119] Comparative Example 2 50 parts by mass of a maleimide compound (A) (MIR-5000, when cured alone, has a dielectric constant of 2.6, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring in the main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and 50 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0120] Comparative Example 3 50 parts by mass of a maleimide compound (A) (MIR-5000, which has a dielectric constant of 2.6 when cured alone, manufactured by Nippon Kayaku Co., Ltd.) having an aromatic ring in the main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, and 50 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is represented by general formula (11) and -(Y-O)n2- is a polymerized structural unit of general formula (14) in general formula (10) were mixed, and the solid content was diluted to 60% by mass with methyl ethyl ketone to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained cured resin plate are shown in Table 2.

[0121] Comparative Example 4 In the general formula (10), X is the general formula (11), and -(Y-O)n2- is a polymerized structural unit of the general formula (14). 50 parts by mass of polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) and 50 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the relative dielectric constant, relative dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin cured plate are shown in Table 2.

[0122] Comparative Example 5 40 parts by mass of a maleimide compound (D) represented by the following general formula (16) (BMI-70, dielectric constant when cured alone is 3.2, manufactured by K.I. Chemicals Co., Ltd.), 35 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X in general formula (10) is general formula (11) and -(Y-O)n2- is a polymerized structural unit of general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and diluted with methyl ethyl ketone to a solid content of 60% by mass to obtain a varnish. The composition of the resin composition is shown in Table 1. Thereafter, a resin-cured plate having a resin layer thickness of 0.3 mm was prepared in the same manner as in Example 1, and the dielectric constant, dielectric loss tangent, peel strength, uniformity of the cured product, and flexibility were evaluated. The evaluation results of the obtained resin-cured plate are shown in Table 2.

[0123] [ka] The maleimide compound (D) represented by the general formula (16) is a compound represented by the general formula (4), 61 ,R 63 is a methyl group, and R 62 ,R 64 is an ethyl group, and R 71 ,R 72 is a hydrogen atom.

[0124] [Table 1]

[0125] [Table 2]

[0126] [Table 3]

[0127] (Measurement and evaluation methods for Examples 1 to 9 and Comparative Examples 1 to 5) (1) Dielectric constant (Dk) and dielectric loss tangent (Df): The copper foil was removed from the resin-cured sheets obtained in each Example and Comparative Example, and the relative dielectric constant and the relative dielectric loss tangent at 10 GHz were measured using a perturbation method cavity resonator (CP-531, product of Kanto Electronics Application Development Co., Ltd.). (2) Copper foil peel strength: For the resin-cured boards obtained in each Example and Comparative Example, the peel strength of the copper foil was measured in accordance with JIS C6481 using test pieces (30 mm × 150 mm × 0.3 mm) with 12 μm copper foil, with three tests, and the average of the lower limit values ​​was taken as the measured value. (3) Uniformity of the cured product: The cross section of the resin cured plate obtained in each Example and Comparative Example was polished with BUEHLER's MetaServ3000, and the state of the cross section was observed with Nikon's EPIPHOT. Those in which voids and poor dispersion were observed were rated as NG, and those in which no voids or poor dispersion were observed were rated as OK. (4) Flexibility evaluation: For the semi-cured copper-attached resin sheets having a resin thickness of 30 μm obtained in each Example and Comparative Example, a cylindrical mandrel bending test was carried out in accordance with JIS K5600-5-1, and the diameter of the mandrel at which the resin first cracked was recorded.

[0128] (Results of Examples 1 to 9 and Comparative Examples 1 to 5) As shown in Table 2, Comparative Example 1 and Comparative Example 5, in which the maleimide compound (D) was mixed in place of the maleimide compound (A), had higher relative dielectric constants and dielectric loss tangents than this Example. Comparative Example 2, in which the polyphenylene ether compound (B) was not mixed, had poor uniformity of the cured product and had a lower peel strength than this Example. Comparative Example 3, in which the styrene-butadiene block copolymer (C) was not mixed, had poor flexibility and a lower peel strength than this Example. Comparative Example 4, in which the maleimide compound (A) and the maleimide compound (D) were not mixed, had a low relative dielectric constant but a lower peel strength than this Example. That is, it was confirmed that by using the resin composition of the present invention, excellent low dielectric constant, low dielectric tangent, peel strength, and flexibility can be obtained, and a uniform cured product can be obtained.

[0129] Example 10 40 parts by mass of a maleimide compound (A) represented by the general formula (6) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.), 35 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X in the general formula (10) is the general formula (11) and -(Y-O)n2- is the polymerized structural unit of the general formula (14), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and coated on an E-glass fiber substrate, and dried by heating at 165 ° C for 3 minutes to obtain a prepreg with a resin composition content of 68 vol % and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0130] Example 11 25 parts by mass of a maleimide compound (A) represented by general formula (6) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.), 35 parts by mass of a polyphenylene ether compound (B) in which X is represented by general formula (11) and -(Y-O)n2- is a polymerized structural unit of general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), and 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was applied to an E-glass fiber substrate by impregnation and then dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0131] Example 12 15 parts by mass of a maleimide compound (A) represented by the general formula (6) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.), 15 parts by mass of a polyphenylene ether compound (B) in which, in the general formula (10), X is represented by the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenylphosphate) (PX-200, Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E), and 30 parts by mass of a biphenyl-type maleimide compound (D) (MIR-3000, Nippon Kayaku Co., Ltd.) in which R501, R502, R503, R504, R505, R506, R507, R508, R509, R510, R511, and R512 are hydrogen atoms and the average value of n5 is 1.4 in the general formula (3) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and coated on an E-glass fiber substrate, and dried by heating at 165 ° C. for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 4.

[0132] Example 13 40 parts by mass of a maleimide compound (A) represented by the general formula (27) (X9-450, manufactured by DIC Corporation), 35 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and applied to an E glass fiber substrate, and dried by heating at 165 ° C for 3 minutes to obtain a prepreg with a resin composition content of 68 vol % and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0133] Example 14 25 parts by mass of a maleimide compound (A) represented by the general formula (27) (X9-450, manufactured by DIC Corporation), 35 parts by mass of a polyphenylene ether compound (B) in which, in the general formula (10), X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Company, Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%), and 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenyl phosphate) (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. The varnish was applied to an E-glass fiber substrate by impregnation and then dried at 165° C. for 3 minutes to obtain a prepreg having a resin composition content of 68% by volume and a thickness of approximately 0.1 mm. The composition of the resin composition is shown in Table 6.

[0134] Example 15 15 parts by mass of a maleimide compound (A) represented by the general formula (27) (X9-450, manufactured by DIC Corporation), 15 parts by mass of a polyphenylene ether compound (B) in which, in the general formula (10), X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Company, Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%). 15 parts by mass of 1,3-phenylenebis(2,6-di-xylenylphosphate) (PX-200, Daihachi Chemical Industry Co., Ltd.) as a phosphorus-based flame retardant (E), and 30 parts by mass of a biphenyl-type maleimide compound (D) (MIR-3000, Nippon Kayaku Co., Ltd.) in which R501, R502, R503, R504, R505, R506, R507, R508, R509, R510, R511, and R512 are hydrogen atoms and the average value of n5 is 1.4 in the general formula (3) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and coated on an E-glass fiber substrate, and dried by heating at 165 ° C. for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0135] (Example 16) 40 parts by mass of a maleimide compound (A) represented by the general formula (27) (X9-470, manufactured by DIC Corporation), 35 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and applied to an E glass fiber substrate, and dried by heating at 165 ° C for 3 minutes to obtain a prepreg with a resin composition content of 68 vol % and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0136] (Example 17) 15 parts by mass of a maleimide compound (A) represented by the general formula (27) (X9-450, manufactured by DIC Corporation); 15 parts by mass of a polyphenylene ether compound (B) in which, in the general formula (10), X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Company, Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.); 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%); 15 parts by mass of olefin bis(2,6-di-xylenyl phosphate) (PX-200, Daihachi Chemical Industry Co., Ltd.), 29 parts by mass of a biphenyl-type maleimide compound (D) (MIR-3000, Nippon Kayaku Co., Ltd.) in which R501, R502, R503, R504, R505, R506, R507, R508, R509, R510, R511, and R512 are hydrogen atoms in the general formula (3) and the average value of n5 is 1.4, and 1 part by mass of a cyanate ester compound (SNCN) (F) obtained from Synthesis Example 1 described in Example 7 were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and coated on an E-glass fiber substrate, and dried by heating at 165 ° C. for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0137] (Example 18) 15 parts by mass of a maleimide compound (A) represented by the general formula (27) (X9-470, manufactured by DIC Corporation); 15 parts by mass of a polyphenylene ether compound (B) in which, in the general formula (10), X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Company, Inc., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.); 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%); 15 parts by mass of olefin bis(2,6-di-xylenyl phosphate) (PX-200, Daihachi Chemical Industry Co., Ltd.), 29 parts by mass of a biphenyl-type maleimide compound (D) (MIR-3000, Nippon Kayaku Co., Ltd.) in which R501, R502, R503, R504, R505, R506, R507, R508, R509, R510, R511, and R512 are hydrogen atoms in the general formula (3), and the average value of n5 is 1.4, and 1 part by mass of a cyanate ester compound (SNCN) (F) obtained from Synthesis Example 1 shown in Example 8 were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and coated on an E-glass fiber substrate, and dried by heating at 165 ° C. for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 6.

[0138] Comparative Example 6 50 parts by mass of maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) and 50 parts by mass of polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is general formula (11) and -(Y-O)n2- is a polymerized structural unit of general formula (14) in general formula (10) were mixed, and the varnish was impregnated and coated on an E-glass fiber substrate, followed by heating and drying at 165°C for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 3.

[0139] Comparative Example 7 50 parts by mass of maleimide compound (A) (MIR-5000, manufactured by Nippon Kayaku Co., Ltd.) and 50 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) were mixed, and the varnish was impregnated and coated on an E-glass fiber substrate, followed by heating and drying at 165°C for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of approximately 0.1 mm. The composition of the resin composition is shown in Table 3.

[0140] Comparative Example 8 In the general formula (10), X is the general formula (11), and -(Y-O)n2- is a polymerized structural unit of the general formula (14). 50 parts by mass of polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) and 50 parts by mass of styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Corporation, styrene ratio 52%) were mixed, and the varnish was impregnated and coated on an E-glass fiber substrate, followed by heating and drying at 165°C for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 3.

[0141] Comparative Example 9 40 parts by mass of the maleimide compound (D) (BMI-70, manufactured by K.I. Chemicals Co., Ltd.) represented by the general formula (16) used in Comparative Example 5, 35 parts by mass of a polyphenylene ether compound (B) (OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 2200, vinyl group equivalent: 1100 g / eq.) in which X is the general formula (11) and -(Y-O)n2- is a polymerized structural unit of the general formula (14) in the general formula (10), and 25 parts by mass of a styrene-butadiene block copolymer (C) (TR2250, manufactured by JSR Co., Ltd., styrene ratio 52%) were mixed and dissolved in methyl ethyl ketone to obtain a varnish. This varnish was impregnated and applied to an E glass fiber substrate, and dried by heating at 165°C for 3 minutes to obtain a prepreg with a resin composition content of 68% by volume and a thickness of about 0.1 mm. The composition of the resin composition is shown in Table 3.

[0142] (Preparation of Evaluation Samples in Examples 10 to 18 and Comparative Examples 6 to 9) Eight prepregs were stacked for each of the prepregs obtained in Examples 10 to 18 and Comparative Examples 6 to 9, and copper foil (3EC-M3-VLP, manufactured by Mitsui Mining & Smelting Co., Ltd., thickness 12 μm) was placed on both the top and bottom surfaces. Lamination molding (thermosetting) was then performed at a pressure of 5 kgf / cm2 and a temperature of 230°C for 100 minutes to obtain a copper foil-clad laminate with an insulating layer thickness of approximately 0.8 mm.

[0143] (Evaluation of moldability in Examples 10 to 18 and Comparative Examples 6 to 9) The copper foil-clad laminates obtained in each Example and Comparative Example were etched to remove voids and poor dispersion on the surface and cross section, and those with no voids or poor dispersion were rated as NG and OK, respectively. The results are shown in Table 5. Note that voids refer to the generation of spaces where no glass fibers or cured resin exist.

[0144] (Evaluation of the relative dielectric constant and the relative dielectric loss tangent in Examples 10 to 18 and Comparative Examples 6 to 9) The copper foil-clad laminates obtained in each Example and Comparative Example were cut into a size of 100 mm x 1.0 mm with a dicing saw, and the copper foil on the surface was removed by etching to obtain a measurement sample. The relative dielectric constant and the relative dielectric loss tangent at 10 GHz were measured using this sample with a perturbation method cavity resonator (Kanto Electronics Application Development Co., Ltd. product, CP-531). The measurement results obtained are shown in Table 5.

[0145] (Evaluation of beer strength in Examples 10 to 18 and Comparative Examples 6 to 9) The copper foil-clad laminates obtained in each Example and Comparative Example were cut to a size of 150 mm × 30 mm using a dicing saw, and the copper foil peel strength was measured in three tests in accordance with JIS C6481, and the average of the lower limit values ​​was taken as the measured value. The results are shown in Table 5.

[0146] [Table 4]

[0147] [Table 5]

[0148] [Table 6]

[0149] As shown in Tables 4 to 6, in the resin compositions described in Examples 10 to 18 that are impregnated into or applied to a glass fiber substrate, in the prepregs containing the maleimide compound (A) having an aromatic main skeleton, the polyphenylene ether compound (B), and the block copolymer (C) having a styrene skeleton, or the maleimide compound (A), the polyphenylene ether compound (B), the block copolymer (C) having a styrene skeleton, and the maleimide compound (D), it was confirmed that the laminate obtained by heat curing had no molding defects, and had a relative dielectric constant of 3.5 or less, a relative dielectric tangent of 0.0043 or less, and a peel strength of 0.6 kN / m.

[0150] In contrast, in the resin composition impregnated or applied to a glass fiber substrate as described in Comparative Example 6, it was confirmed that in the prepreg containing a maleimide compound (A) having an aromatic main skeleton and a polyphenylene ether compound (B), the laminate obtained by heat curing had a higher dielectric constant and a higher dielectric loss tangent than those in this example, and a lower peel strength than those in this example.

[0151] In the resin composition impregnated or applied to a glass fiber substrate as described in Comparative Example 7, it was confirmed that in the prepreg containing a maleimide compound (A) having an aromatic main skeleton and a block copolymer (C) having a styrene skeleton, molding defects occurred in the laminate obtained by heat curing, and it was impossible to measure the relative dielectric constant, relative dielectric tangent, and peel strength.

[0152] In the resin composition impregnated or applied to a glass fiber substrate as described in Comparative Example 8, it was confirmed that in the prepreg containing a polyphenylene ether compound (B) having an aromatic main skeleton and a block copolymer (C) having a styrene skeleton, molding defects occurred in the laminate obtained by heat curing, and it was impossible to measure the relative dielectric constant, relative dielectric tangent, and peel strength.

[0153] In the resin composition impregnated or applied to a glass fiber substrate as described in Comparative Example 9, it was confirmed that the laminate obtained by heat curing in the prepreg containing the maleimide compound (D) having an aromatic main skeleton, the polyphenylene ether compound (B), and the block copolymer (C) having a styrene skeleton had a higher dielectric constant and dielectric loss tangent than those in this example.

[0154] That is, it was confirmed that, according to this example, excellent moldability, low dielectric constant characteristics, low dielectric loss tangent, and peel strength could be obtained. [Industrial Applicability]

[0155] As described above, the resin composition of the present invention can be widely and effectively used in various applications such as electric / electronic materials, machine tool materials, and aviation materials, for example, as electric insulating materials, semiconductor plastic packages, sealing materials, adhesives, laminate materials, resists, and build-up laminate materials. In particular, the resin composition can be particularly effectively used as a printed wiring board material compatible with the high integration and densification of recent information terminal devices, communication devices, and the like.

Claims

1. The composition contains a maleimide compound (A) having an aromatic ring in its main skeleton and exhibiting a relative dielectric constant of less than 2.7 at 10 GHz when cured alone, a polyphenylene ether compound (B) represented by the following general formula (1) and having a number average molecular weight of 1,000 or more and 7,000 or less, and a block copolymer (C) having a styrene skeleton, The maleimide compound (A) is at least one selected from the group consisting of compounds represented by the following general formula (22), and contains at least one compound other than the compound in which nx of the following general formula (22) is 0: 【Chemistry 1】 (In the above general formula (1), X represents an aryl group, and -(Y-O)n 2 - represents a polyphenylene ether moiety, R 1 , R 2 , R 3 each independently represents a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group; 2 represents an integer from 1 to 100, n 1 represents an integer from 1 to 6; n 3 represents an integer from 1 to 4.) 【Chemistry 2】 (In the above general formula (22), R M1 , R M2 , R M3 , and R M4 each independently represent a hydrogen atom or an organic group. R M5 and R M6 each independently represent a hydrogen atom or an alkyl group. Ar M represents a divalent aromatic group. A is a 4- to 6-membered alicyclic group. R M7 and R M8 each independently represent an alkyl group. mx is 1 or 2, and lx is 0 or 1. R M9 and R M10 each independently represent a hydrogen atom or an alkyl group. R M11 , R M12 , R M13 , and R M14 each independently represent a hydrogen atom or an organic group. nx represents an integer of 0 or more and 20 or less.)

2. The resin composition according to claim 1, wherein the maleimide compound (A) comprises two or more compounds having different values ​​of nx in the general formula (22), and the average value of nx is 0.95 or more and 10.0 or less.

3. The resin composition according to claim 1, wherein the block copolymer (C) having a styrene skeleton contains at least one selected from the group consisting of a styrene-butadiene block copolymer, a styrene-isoprene block copolymer, a styrene-hydrogenated butadiene block copolymer, a styrene-hydrogenated isoprene copolymer, and a styrene-hydrogenated (isoprene / butadiene) copolymer.

4. The resin composition according to claim 1 , further comprising a maleimide compound (D) other than the maleimide compound (A).

5. The resin composition according to claim 4, wherein the maleimide compound (D) contains at least one selected from the group consisting of the following general formulas (2), (3), (4) and (5). 【Chemistry 3】 (In the above general formula (2), R 41 , R 42 each independently represents a hydrogen atom or a methyl group; 4 indicates an integer of 1 or more.) 【Chemistry 4】 (In the above general formula (3), R 501 , R 502 , R 503 , R 504 , R 505 , R 506 , R 507 , R 508 , R 509 , R 510 , R 511 , R 512 each independently represents a hydrogen atom, an alkyl group having 1 to 8 carbon atoms, or a phenyl group; 5 indicates an integer of 1 or more and 10 or less.) 【Chemistry 5】 (In the above general formula (4), R 61 , R 62 , R 63 , R 64 each independently represents a hydrogen atom, a methyl group, or an ethyl group; R 71 , R 72 each independently represents a hydrogen atom or a methyl group. 【Chemistry 6】 (In the above general formula (5), R 81 , R 82 each independently represents a hydrogen atom, a methyl group, or an ethyl group.

6. The resin composition according to claim 1 , further comprising a flame retardant (E).

7. The resin composition according to claim 1 , further comprising a cyanate ester compound (F).

8. A resin sheet comprising a support and a layer formed from the resin composition according to claim 1 disposed on a surface of the support.

9. A prepreg comprising a substrate and the resin composition according to claim 1 impregnated into or applied to the substrate.

10. A printed wiring board comprising an insulating layer and a conductor layer disposed on a surface of the insulating layer, the insulating layer comprising a layer formed from the resin composition according to claim 1.

Citation Information

Patent Citations

  • Resin composition, prepreg, metal foil-clad laminate, resin sheet and printed wiring board

    WO2019230945A1

  • Resin composition and applications thereof

    WO2020004211A1

Cited By

  • Resin composition, prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board

    JPWO2022054861A1